Metal wiring manufacturing method
The method addresses the complexity and inefficiencies of conventional metal wiring manufacturing by using a dispersion-based coating, laser irradiation, and a two-stage development process, resulting in high-quality, low-resistance metal wiring with minimal variation.
Patent Information
- Application Number
- JP2022052441
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-04-30
- Filing Date
- 2022-03-28
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-03-28
AI Technical Summary
Conventional methods for manufacturing metal wiring on circuit boards are complex, require multiple steps, and involve the use of photoresist material, leading to issues like growth of metal outside the target pattern, short circuits, and damage to wiring during development.
A method involving a coating step with a dispersion of metal particles or metal oxide particles, followed by drying, laser light irradiation to form metal wiring, and a two-stage development process using specific developers to remove unwanted coating while minimizing damage to the wiring.
The method effectively reduces the change in resistance value of metal wiring before and after development, allows for the reuse and removal of coating material, and produces high-quality metal wiring with low resistance and minimal variation in resistance values.
Smart Images

Figure 0007650842000006 
Figure 0007650842000007 
Figure 0007650842000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing metal wiring. [Background technology]
[0002] A circuit board has a structure in which conductive wiring is applied onto a substrate. The manufacturing method of a circuit board is generally as follows. First, a photoresist is applied onto a substrate to which a metal foil has been attached. Next, the photoresist is exposed to light and developed to obtain a negative shape of a desired circuit pattern. Next, the metal foil not covered by the photoresist is removed by chemical etching to form a pattern. This allows the manufacture of a high-performance conductive substrate.
[0003] However, the conventional methods have drawbacks such as the large number of steps, the complexity, and the need for a photoresist material.
[0004] In response to this, a direct wiring printing technique has been attracting attention, in which a desired wiring pattern is directly printed on a substrate using a dispersion (hereinafter also referred to as a "paste material") in which particles selected from the group consisting of metal particles and metal oxide particles are dispersed. This technique has a small number of steps, does not require the use of photoresist materials, and is therefore extremely productive.
[0005] One example of a direct printed wiring technology is a method in which a paste material is applied to the entire surface of a substrate to form a coating film, and then the coating film is irradiated with laser light in a pattern to selectively thermally bake it, thereby obtaining a desired wiring pattern (see, for example, Patent Documents 1 and 2).
[0006] Patent Document 2 describes that when drawing was performed by irradiating a GaAlAs laser beam with a wavelength of 830 nm, the beam diameter on the copper oxide thin film was 5 μm, and the copper oxide was reduced in the area irradiated with the laser beam due to local heating, forming a reduced copper region with a diameter of approximately 5 μm. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2010 / 024385 [Patent Document 2] Japanese Patent Application Publication No. 5-37126 Summary of the Invention [Problem to be solved by the invention]
[0008] When forming wiring by drawing with laser light irradiation as described above, a coating film remains in the area not irradiated with light. This remaining coating film can cause problems such as metal growth outside the intended wiring pattern and short circuits due to migration during plating operations after wiring formation. Therefore, after laser light irradiation, it is necessary to thoroughly remove the remaining coating film by a development operation.
[0009] The effect of removing the remaining coating film is enhanced by applying a physical force, such as by irradiating ultrasonic waves in the developer during development, but on the other hand, such a physical force can damage the metal wiring, leading to problems such as disconnection of the metal wiring or an increase in resistance value.
[0010] The present invention has been made in view of the above-mentioned points, and aims to provide a method for manufacturing metal wiring that can reduce the change in resistance value of the metal wiring before and after development while sufficiently removing the coating film remaining between the metal wiring in the development step, thereby making it possible to manufacture high-quality metal wiring (more specifically, low resistance and small variation in resistance value between parts).Furthermore, a specific embodiment of the present invention aims to effectively utilize resources by removing and reusing the coating film remaining between the metal wiring. [Means for solving the problem]
[0011] The present disclosure encompasses the following aspects. [1] A coating step of coating a surface of a substrate with a dispersion containing a particle component that is a metal particle and / or a metal oxide particle to form a dispersion layer; drying the dispersion layer to form a dried coated structure having the substrate and a dried coating disposed on the substrate; a laser light irradiation step of irradiating the dried coating film with a laser light to form metal wiring; A developing step of developing and removing an area of the dried coating film other than the metal wiring with a developer, The developing step comprises: (1) a first development process in which the dried coating film is developed with a first developer; and (2) a second development process in which the dried coating film is developed with a second developer; Including, A method for producing metal wiring, wherein the first developer and the second developer each contain water and / or an organic solvent. [2] The first developer contains water and / or an alcohol-based solvent; 2. The method for producing a metal wiring according to item 1, wherein the second developer contains an organic solvent. [3] The method for producing a metal wiring according to item 1 or 2 above, wherein the first developer and / or the second developer contains an alcohol-based solvent. [4] The method for producing a metal wiring according to any one of items 1 to 3 above, wherein the first developer and / or the second developer contains an amine-based solvent. [5] The method for producing a metal wiring according to item 4 above, wherein the amine-based solvent contains diethylenetriamine and / or 2-aminoethanol. [6] The method for producing a metal wiring according to any one of items 1 to 5 above, wherein the first developer and / or the second developer contains 0.1 mass % or more and 20 mass % or less of a dispersant (A). [7] The method for producing a metal wiring according to item 6, wherein the dispersant (A) is a phosphorus-containing organic compound. [8] The method for producing a metal wiring according to item 6 or 7 above, wherein the dispersion contains a dispersant (B), and the main components of the dispersant (A) and the dispersant (B) are the same. [9] The method for producing a metal wiring according to any one of items 1 to 8 above, wherein the difference between the surface free energy of the first developer and the surface free energy of the dispersion is 0 mN / m or more and 50 mN / m or less.
[10] The method for producing a metal wiring according to any one of items 1 to 9 above, wherein the solubility of the particulate component in the second developer is higher than the solubility of the particulate component in the first developer.
[11] The method for producing a metal wiring according to any one of items 1 to 10, wherein the particle component is copper particles and / or copper oxide particles.
[12] The method for producing a metal wiring according to item 11 above, wherein the solubility of the particle component in the second developer is 0.1 mg / L or more and 10,000 mg / L or less.
[13] The method for producing a metal wiring according to any one of items 1 to 12, further comprising recovering a used developer after the developing step.
[14] The method for producing a metal wiring according to any one of items 1 to 13, wherein the dispersion is prepared from a solution containing a used developer recovered after the developing step.
[15] A kit comprising a dried coated structure and a developer, The dry coated structure has a substrate and a dry coating film that includes a particulate component, which is a metal particle and / or a metal oxide particle, and is disposed on a surface of the substrate; the developer comprises a first developer and a second developer, wherein each of the first developer and the second developer comprises water and / or an organic solvent.
[16] The kit according to item 15, wherein the organic solvent is an alcohol-based solvent.
[17] The kit according to item 15 or 16, wherein the first developer and / or the second developer contain 0.1% by mass or more and 20% by mass or less of a dispersant (A).
[18] The kit according to item 17, wherein the dried coating film contains a dispersant (B), and the main components of the dispersant (A) and the dispersant (B) are the same.
[19] A coating mechanism for coating a dispersion containing a particle component, which is a metal particle and / or a metal oxide particle, on a surface of a substrate to form a dispersion layer; a drying mechanism for drying the dispersion layer to form a dried coated structure having the substrate and a dried coating disposed on the substrate; a laser light irradiation mechanism for irradiating the dried coating film with a laser light to form metal wiring; a developing mechanism for developing and removing an area of the dried coating film other than the metal wiring with a developer; A metal wiring manufacturing system comprising: The developing mechanism includes: (1) a first developing section for developing the dried coating film with a first developer; and (2) a second developing section for developing the dried coating film with a second developer; having A metal wiring manufacturing system, wherein each of the first developer and the second developer contains water and / or an organic solvent.
[20] The metal wiring manufacturing system according to item 19, wherein the organic solvent is an alcohol-based solvent.
[21] The metal wiring manufacturing system according to item 19 or 20, wherein the first developer and / or the second developer contain 0.1 mass % or more and 20 mass % or less of a dispersant (A). Effect of the Invention
[0012] According to one aspect of the present invention, a method for producing metal wiring can be provided that can reduce the change in resistance value of the metal wiring before and after development while sufficiently removing the coating film remaining between the metal wiring in the development step, thereby producing high-quality metal wiring (more specifically, low resistance and small variation in resistance value between parts). Furthermore, according to a specific aspect of the present invention, resources can be effectively utilized by removing and reusing the coating film remaining between the metal wiring. [Brief description of the drawings]
[0013] [Figure 1] 1A to 1C are explanatory diagrams showing an example of a method for manufacturing a metal wiring according to an embodiment of the present invention. [Diagram 2] 5A to 5C are schematic diagrams illustrating overlapping irradiation of laser light in the method for manufacturing metal wiring according to the embodiment. [Diagram 3] 4 is a schematic diagram showing an example of a jig for holding a conductive portion-attached structure in a development step of the method for producing metal wiring according to the present embodiment. FIG. [Figure 4] 4 is a schematic diagram showing an example of a jig for holding a conductive portion-attached structure in a development step of the method for producing metal wiring according to the present embodiment. FIG. [Diagram 5] 4 is a schematic diagram showing an example of a jig for holding a conductive portion-attached structure in a development step of the method for producing metal wiring according to the present embodiment. FIG. [Figure 6] 1A to 1C are explanatory diagrams showing an example of reusing a used developer in the method for manufacturing a metal wiring according to the present embodiment. [Figure 7] 1A to 1C are explanatory diagrams showing an example of a process flow in the case where a used developer is reused in the method for manufacturing a metal wiring according to the present embodiment. [Figure 8] FIG. 1 is an explanatory diagram illustrating an example of a metal wiring manufacturing system according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the present invention (hereinafter, abbreviated as "the present embodiment") will be described in detail, but the present invention is not limited to this embodiment.
[0015] <Metal Wiring Manufacturing Method> One aspect of the present invention is A coating step of coating a dispersion containing a particle component (sometimes simply referred to as a particle component in this disclosure) that is a metal particle and / or a metal oxide particle on a surface of a substrate to form a dispersion layer; drying the dispersion layer to form a dried coated structure having a substrate and a dried coating disposed on the substrate; a laser light irradiation step of irradiating the dried coating film with a laser light to form metal wiring; and a developing step of developing and removing the area of the dried coating film other than the metal wiring with a developer. In one embodiment, the developing step comprises: (1) a first development process for developing the dried coating film with a first developer; and (2) a second development step in which the dried coating is developed with a second developer; In one embodiment, the first developer and the second developer comprise water and / or an organic solvent.
[0016] The present inventors have noticed that when forming a metal wiring in a region of a dry coating film arranged on a substrate that has been irradiated with laser light (hereinafter, also referred to as an exposed portion) and developing and removing a region of the dry coating film that has not been irradiated with laser light (hereinafter, also referred to as an unexposed portion) with a developer, the unexposed portion may not be sufficiently removed by the developer, and the metal wiring may be damaged or peeled off by development. As a result of examining various means for avoiding these problems, the present inventors have found that by using a first and a second developer having specific compositions in combination, it is possible to achieve both good development and removal of the unexposed portion and the formation of a metal wiring that has low resistance and little variation in resistance value between parts.
[0017] [Developer composition] In the method of the present embodiment, at least two developers are used: a first developer containing water and / or an organic solvent, and a second developer containing water and / or an organic solvent. From the viewpoint of improving developability, the developer preferably contains a dispersant (dispersant (A) of the present disclosure). The dispersant can efficiently disperse metal particles and / or metal oxide particles attached to the substrate in the developer (i.e., efficiently remove them). The dispersant may be contained in one or both of the first developer and the second developer, but when the dispersant is contained only in the developer used in the preceding development process (in one embodiment, the first developer when developing is performed in the order of the first development process and the second development process), it is advantageous from the viewpoint of recyclability because the particles can be efficiently recovered in one go.
[0018] As the dispersant, it is preferable to use one whose main component is the same as that of the dispersant contained in the dispersion of the present disclosure. In the present disclosure, the main component of the dispersant is the component that exists in the largest amount among the components present as a dispersant in the dispersion or the developer. When the main component of the dispersant in the dispersion and the main component of the dispersant in the developer are the same, the developability is improved. Furthermore, the developer can be recovered and reused as a dispersion. As the dispersant that the dispersion of the present disclosure may contain, those described later in the section [Composition of the Dispersion and the Dried Coating] are preferable. For example, when a phosphorus-containing organic compound is used, metal particles and / or metal oxide particles (especially copper oxide particles) are well dispersed in the developer, so that development is easy. Therefore, in one embodiment, suitable compound examples of the dispersant in the developer are the same as suitable compound examples of the dispersant described later in the section [Composition of the Dispersion and the Dried Coating].
[0019] The content of the dispersant in the developer is preferably 0.1% by mass or more, or 0.5% by mass or more, or 1.0% by mass or more, in order to efficiently disperse metal particles and / or metal oxide particles adhered to the substrate in the developer (i.e., to efficiently remove them), and is preferably 20% by mass or less, or 15% by mass or less, or 10% by mass or less, in order to suppress dissolution of metal wiring by the dispersant, to form a low-viscosity developer suitable for development even when a high-viscosity dispersant is used, and to prevent excess dispersant from adhering to the substrate and metal wiring and simplify the water washing step after development.
[0020] The first developer and the second developer contain water and / or an organic solvent. The organic solvent can dissolve and remove metal or metal oxide, so that it can prevent metal from remaining between wirings and is suitable for finish development. As the organic solvent, amine-based solvents, alcohol-based solvents, hydrocarbon-based solvents, ester-based solvents, ketone-based solvents, etc. are suitable, and these may be used alone or in combination of two or more.
[0021] Examples of amine solvents include amines (primary amines, secondary amines, and tertiary amines), alkanolamines, amides, and the like. More specific examples include diethylenetriamine, 2-aminoethanol, diethanolamine, triethanolamine, monoisopropanolamine, diisopropanolamine, triisopropanolamine, N-methylethanolamine, N-methyldiethanolamine, dicyclohexylamine, n-methyl-2-pyrrolidone, and N,N-dimethylformamide.
[0022] Examples of the alcohol-based solvent include monohydric or polyhydric alcohols, and ethers and esters of the alcohols. The alcohol is preferably glycol. More specific examples of the alcohol-based solvent include: Monohydric alcohols such as methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, sec-butanol, t-butanol, n-pentanol, i-pentanol, sec-pentanol, t-pentanol, 2-methylbutanol, 2-ethylbutanol, 3-methoxybutanol, n-hexanol, sec-hexanol, 2-methylpentanol, sec-heptanol, 3-heptanol, n-octanol, sec-octanol, 2-ethylhexanol, n-nonyl alcohol, 2,6-dimethyl-4-heptanol, n-decanol, cyclohexanol, methylcyclohexanol, 3,3,5-trimethylcyclohexanol, phenol, benzyl alcohol, and diacetone alcohol; glycols such as ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 2-pentanediol, 2-methylpentane-2,4-diol, 2,5-hexanediol, 2,4-heptanediol, 2-ethylhexane-1,3-diol, diethylene glycol, dipropylene glycol, hexanediol, octanediol, triethylene glycol, tri-1,2-propylene glycol, etc.; polyhydric alcohols such as glycerin, etc.; glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol tertiary butyl ether, and dipropylene glycol monomethyl ether; Glycol esters such as propylene glycol monomethyl ether acetate; etc.
[0023] Examples of the hydrocarbon solvent include pentane, hexane, octane, nonane, decane, cyclohexane, methylcyclohexane, toluene, xylene, mesitylene, and ethylbenzene.
[0024] Examples of the ester solvent include 3-methoxy-3-methyl-butyl acetate, ethoxyethyl propionate, glycerol ethyl acetate, n-propyl acetate, and isopropyl acetate.
[0025] Examples of the ketone solvent include methyl ethyl ketone, methyl isobutyl ketone, and dimethyl carbonate.
[0026] In a preferred embodiment, the organic solvent includes or is an alcohol-based solvent. Water or an alcohol-based solvent is a solvent in which a dispersant can be dispersed well, and by combining with the dispersant, the redispersibility of the particles on the substrate is improved, so that the water or alcohol-based solvent is suitable for dispersing metal particles and / or metal oxide particles attached to the substrate in the developer. As the alcohol-based solvent, from the viewpoint of efficient removal of particles, alcohols having 10 or less carbon atoms are preferred, and ethanol, n-butanol, n-heptanol, and n-octanol are particularly preferred.
[0027] In a preferred embodiment, the first developer contains water and / or an alcohol-based solvent, and the second developer contains an organic solvent. Also, in a preferred embodiment, the first developer and / or the second developer contain an alcohol-based solvent.
[0028] The content of the alcohol-based solvent in each of the first developer and the second developer may be, in one embodiment, 1% by mass or more, or 2% by mass or more, or 3% by mass or more, or 5% by mass or more, or 10% by mass or more, or 20% by mass or more, or 30% by mass or more, and in one embodiment, 99% by mass or less, or 98% by mass or less, or 97% by mass or less, or 95% by mass or less.
[0029] The total content of water and alcohol-based solvent in each of the first developer and the second developer may be 20% by mass or more, 40% by mass or more, 50% by mass or more, or 60% by mass or more in one embodiment. The total content may be 100% by mass in one embodiment, or 99% by mass or less, 98% by mass or less, or 97% by mass or less in one embodiment.
[0030] In a preferred embodiment, the organic solvent contains or is an amine-based solvent from the viewpoint of developability. In a preferred embodiment, the first developer and / or the second developer contains an amine-based solvent. In a particularly preferred embodiment, when a first development process using the first developer is followed by a second development process using the second developer, the second developer contains an amine-based solvent. Specific examples of suitable amine-based solvents include diethylenetriamine, 2-aminoethanol, diethanolamine, triethanolamine, monoisopropanolamine, diisopropanolamine, triisopropanolamine, N-methylethanolamine, N-methyldiethanolamine, dicyclohexylamine, n-methyl-2-pyrrolidone, and N,N-dimethylformamide. In terms of developability, it is particularly preferred that the amine-based solvent contains at least one of diethylenetriamine and 2-aminoethanol.
[0031] In one embodiment, the water content of each of the first developer and the second developer may be 1% by mass or more, or 2% by mass or more, or 3% by mass or more, or 5% by mass or more, or 10% by mass or more, or 20% by mass or more, or 30% by mass or more. The water content may be 100% by mass in one embodiment, or may be 99% by mass or less, or 98% by mass or less, or 97% by mass or less, or 95% by mass or less.
[0032] In one embodiment, the content of the organic solvent in each of the first developer and the second developer may be 1% by mass or more, or 2% by mass or more, or 3% by mass or more, or 5% by mass or more, or 10% by mass or more, or 20% by mass or more, or 30% by mass or more. In one embodiment, the content may be 100% by mass, or in one embodiment, 99% by mass or less, or 98% by mass or less, or 97% by mass or less, or 95% by mass or less. In this case, the remainder may include water and / or a dispersant.
[0033] (Solubility) In one embodiment, the solubility of the particle component (i.e., metal particles and / or metal oxide particles contained in the dispersion) in the second developer is preferably higher than the solubility of the particle component in the first developer. The solubility is a value based on metal measured by inductively coupled plasma (ICP) emission spectrometry. When metal particles and metal oxide particles are present in the dispersion at a ratio of metal particles:metal oxide particles=A:B (mass ratio), the solubility refers to the solubility based on metal of the mixture of metal particles and metal oxide particles at an A:B (mass ratio). The specific evaluation procedure for the solubility is as follows. 0.10 g of powder of the particle component, which is metal particles and / or metal oxide particles, is added to 40 ml of the developer and allowed to stand at room temperature of 25° C. for 6 hours. Thereafter, the developer containing the powder is filtered through a 0.2 μm filter and diluted 100 times (by mass) with 0.10 mol / L nitric acid. The metal concentration (unit: mg / L) of the obtained diluted solution is measured using an ICP light emitting device (e.g., manufactured by SII NanoTechnology). From the metal concentration, the metal-based concentration (unit: mg / L) of the particle component is calculated and used as the solubility of the particle component. According to the above solubility, by performing development with the second developer after development with the first developer, good development removal efficiency of metal particles and / or metal oxide particles attached to the substrate can be obtained.
[0034] In particular, it is preferred that the solubility of the particle components in the second developer is higher than that in the first developer, the first developer contains water and / or an alcohol-based solvent and a dispersant (A), the dispersant (A) is particularly a phosphorus-containing compound, the dispersion contains a dispersant (B), the main components (i.e., the component contained in the largest amount by mass among the additives) of the dispersant (A) and the dispersant (B) are the same, and development with the first developer and then development with the second developer are performed. In this case, the efficiency of development and removal of metal particles and / or metal oxide particles attached to the substrate is particularly good.
[0035] The solubility of the particle component in the first developer, the second developer and any additional developer is preferably 0.1 mg / L or more, or 1.0 mg / L or more, or 10 mg / L or more, or 100 mg / L or more, and preferably 10000 mg / L or less, or 5000 mg / L or less, or 1000 mg / L or less, or 500 mg / L or less. In particular, when the particle component is copper oxide particles, the solubility of copper oxide in the first developer is 0.1 mg / L or more, so that the solubility of copper oxide particles is high and the development effect is high, and the solubility is 5000 mg / L or less, so that the damage to the metal wiring can be particularly well reduced.
[0036] In one embodiment, the solubility of the particle component in the first developer is 0.1 mg / L to 100 mg / L, and the solubility of the particle component in the second developer is 1.0 mg / L to 500 mg / L.
[0037] (Surface Free Energy) The surface free energy of each of the first developer, the second developer and any additional developer is preferably 10 mN / m or more, or 15 mN / m or more, or 20 mN / m or more, and is preferably 75 mN / m or less, or 60 mN / m or less, or 50 mN / m or less. In the present disclosure, the surface free energy is a value measured by a pendant drop method using a contact angle meter.
[0038] The difference between the surface free energy of each of the first developer, the second developer, and any additional developer and the surface free energy of the dispersion is preferably 50 mN / m or less, or 25 mN / m or less, or 10 mN / m or less, from the viewpoint of improving the affinity between the developer and the dried coating film and enhancing the development removal effect. The difference is most preferably 0 mN / m, but may be, for example, 1 mN / m or more, or 5 mN / m or more, from the viewpoint of ease of production of the developer and the dispersion.
[0039] [Composition of dispersion and dried coating] In one embodiment, the dry coating film containing the particle component, which is a metal particle and / or a metal oxide particle, of the present disclosure is formed by applying a dispersion containing the particle component, a dispersion medium, and optionally a dispersant and / or a reducing agent, onto a substrate, and then drying. Therefore, in one embodiment, the mass ratio of the components other than the dispersion medium in the dry coating film may be considered to be the same as the mass ratio of the components other than the dispersion medium in the dispersion. Alternatively, the content of the metal element in the dry coating film can be confirmed by a SEM (scanning electron microscope) and an EDX (energy dispersive X-ray analysis) device.
[0040] The content of the dispersant in the dispersion and in the dried coating film can be confirmed using a TG-DTA (thermogravimetric-differential thermal analysis) device.
[0041] The content of the reducing agent in the dispersion can be confirmed by a surrogate method using a GC / MS (gas chromatography / mass spectrometry) device. Also, the content of the reducing agent in the dried coating film can be confirmed by a surrogate method using a GC / MS device after redispersing the dried coating film in a dispersion medium. The following is a measurement example in which hydrazine is used as the reducing agent.
[0042] (Hydrazine Quantitative Method) In a 50 μL dispersion, 33 μg of hydrazine and a surrogate substance (hydrazine 15 N 2 H 4 Add 33μg of benzaldehyde and 1ml of 1% acetonitrile solution. Finally, add 20μL of phosphoric acid, and after 4 hours, perform GC / MS measurement.
[0043] Similarly, 66 μg of hydrazine and a surrogate substance (hydrazine 15 N 2 H 4 Add 33μg of benzaldehyde and 1ml of 1% acetonitrile solution. Finally, add 20μL of phosphoric acid, and after 4 hours, perform GC / MS measurement.
[0044] Similarly, 133 μg of hydrazine and a surrogate substance (hydrazine 15 N 2 H4 Add 33μg of benzaldehyde and 1ml of 1% acetonitrile solution. Finally, add 20μL of phosphoric acid, and after 4 hours, perform GC / MS measurement.
[0045] Finally, 50 μL of the dispersion was diluted with hydrazine and the surrogate (hydrazine 15 N 2 H 4 ) 33 μg, 1 ml of 1% benzaldehyde solution in acetonitrile, and finally 20 μL of phosphoric acid are added, and after 4 hours, GC / MS measurement is performed.
[0046] From the GC / MS measurements of the above four points, the peak area value of hydrazine is obtained from the chromatogram at m / z = 207. Next, the peak area value of the surrogate is obtained from the mass chromatogram at m / z = 209. The x-axis represents the weight of hydrazine added / the weight of the surrogate substance added, and the y-axis represents the peak area value of hydrazine / the peak area value of the surrogate substance, to obtain a calibration curve using the surrogate method.
[0047] The Y-intercept value obtained from the calibration curve is divided by the weight of hydrazine added / the weight of the surrogate substance added to obtain the weight of hydrazine.
[0048] (i) Metal particles and / or metal oxide particles The metal contained in the particle component, which is a metal particle and / or a metal oxide particle, is aluminum, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, ruthenium, rhodium, palladium, silver, indium, tin, antimony, iridium, platinum, gold, thallium, lead, bismuth, etc., and may be an alloy or a mixture containing one or more of these. In addition, the metal oxide may be an oxide of the metal exemplified above. Among them, silver or copper metal oxide particles are preferred because they are easily reduced when irradiated with a laser beam and can form uniform metal wiring. In particular, copper metal oxide particles are preferred because they are relatively stable in air and can be obtained at low cost, which is advantageous from the viewpoint of business. Copper oxide includes, for example, cuprous oxide and cupric oxide. Cuprous oxide is particularly preferred because it has high absorbance to laser beam, can be sintered at a low temperature, and can form a sintered product with low resistance. The cuprous oxide and the cupric oxide may be used alone or in combination.
[0049] The metal oxide particles in one embodiment include or are copper oxide particles. The copper oxide particles may have a core / shell structure, and either the core or the shell may comprise cuprous oxide and / or cupric oxide.
[0050] The average secondary particle size of each of the metal particles and metal oxide particles (copper oxide particles in one embodiment) is not particularly limited, but is preferably 500 nm or less, or 200 nm or less, or 100 nm or less, or 80 nm or less, or 50 nm or less, or 20 nm or less. The average secondary particle size of the particles is preferably 1 nm or more, or 5 nm or more, or 10 nm or more, or 15 nm or more.
[0051] The average secondary particle diameter is the average particle diameter of an aggregate (secondary particle) formed by gathering a plurality of primary particles. If the average secondary particle diameter is 500 nm or less, it is preferable because fine metal wiring tends to be easily formed on a support. If the average secondary particle diameter is 1 nm or more, particularly 5 nm or more, it is preferable because the long-term storage stability of the dispersion is improved. The average secondary particle diameter of the particles can be measured by a transmission electron microscope or a scanning electron microscope.
[0052] The average primary particle diameter of the primary particles constituting the secondary particles is preferably 100 nm or less, more preferably 50 nm or less, and even more preferably 20 nm or less.The average primary particle diameter is preferably 1 nm or more, more preferably 2 nm or more, and even more preferably 5 nm or more.
[0053] When the average primary particle size is 100 nm or less, the firing temperature, which will be described later, tends to be able to be lowered. The reason why such low-temperature firing is possible is thought to be that the smaller the particle size of the particles, the higher the surface energy, and the lower the melting point.
[0054] In addition, if the average primary particle size is 1 nm or more, good dispersibility can be obtained, which is preferable. When forming a wiring pattern on a substrate, from the viewpoint of adhesion to the base and low resistance, the average primary particle size is preferably 2 nm or more, or 5 nm or more, and preferably 100 nm or less, or 50 nm or less. This tendency is remarkable when the base is a resin. The average primary particle size of the particles can be measured by a transmission electron microscope or a scanning electron microscope.
[0055] The dispersions and dry coatings may include copper particles, i.e., the dispersions and dry coatings of the present disclosure may include copper.
[0056] The dispersion and the dried coating film may contain copper oxide particles and copper particles. In this case, the mass ratio of the copper particles to the copper oxide particles (hereinafter referred to as "copper particles / copper oxide particles") is preferably 1.0 or more, or 1.5 or more, or 2.0 or more, and preferably 7.0 or less, or 6.0 or less, or 5.0 or less, from the viewpoints of electrical conductivity and crack prevention.
[0057] The content of the particle components, which are metal particles and / or metal oxide particles, in the dispersion is the total content of the metal particles and metal oxide particles, and is preferably 0.50% by mass to 60% by mass, more preferably 1.0% by mass to 60% by mass, and even more preferably 5.0% by mass to 50% by mass, relative to 100% by mass of the dispersion. When the total content is 60% by mass or less, aggregation of the metal particles and / or metal oxide particles tends to be easily suppressed. When the total content is 0.50% by mass or more, the metal wiring (i.e., the conductive film) obtained by firing the dried coating film by laser light irradiation tends not to be too thin and has good conductivity.
[0058] The content of the particle components, which are metal particles and / or metal oxide particles, in the dry coating film is preferably 40% by mass or more, more preferably 55% by mass or more, and even more preferably 70% by mass or more, based on 100% by mass of the dry coating film, and the content is preferably 98% by mass or less, more preferably 95% by mass or less, and even more preferably 90% by mass or less.
[0059] The content of the particle components, which are metal particles and / or metal oxide particles, in the dry coating film is preferably 10% by volume or more, more preferably 15% by volume or more, and even more preferably 25% by volume or more, based on 100% by volume of the dry coating film, and is preferably 90% by volume or less, more preferably 76% by volume or less, and even more preferably 60% by volume or less.
[0060] If the content of the particle component in the dry coating film is 40% by mass or more or 10% by volume or more, the particles are fused together by firing to exhibit good electrical conductivity, which is preferable. The higher the concentration of the particle component, the better the electrical conductivity. However, if the content is 98% by mass or less or 90% by volume or less, the dry coating film can adhere well to the substrate to such an extent that the metal wiring can be stably formed, and if the content is 95% by mass or less or 76% by volume or less, the adhesion is stronger, which is preferable. In addition, if the content is 90% by mass or less or 60% by volume or less, the dry coating film has high flexibility, is less likely to crack when bent, and has high reliability.
[0061] ((ii) Dispersant) The dispersions and dried coatings may contain dispersants to improve dispersion of the particulate components which are metal particles and / or metal oxide particles.
[0062] The number average molecular weight of the dispersant is not particularly limited, but is preferably 300 to 300,000, more preferably 300 to 30,000, and even more preferably 300 to 10,000. If the number average molecular weight is 300 or more, the dispersion stability of the dispersion tends to increase, and if it is 300,000 or less, firing during wiring formation is easy, and if it is 30,000 or less, the amount of dispersant remaining after firing is smaller, and the resistance of the metal wiring can be reduced. In the present disclosure, the number average molecular weight is a value obtained by using gel permeation chromatography and converting it into standard polystyrene.
[0063] As the dispersant, a phosphorus-containing organic compound is preferred in terms of excellent dispersibility of metal particles and / or metal oxide particles. In addition, the dispersant preferably has a group (e.g., a hydroxyl group) that has affinity for these particles, from the viewpoint of adsorbing to the metal particles and / or metal oxide particles and suppressing particle aggregation by a steric hindrance effect. In particular, a combination of metal oxide particles and a hydroxyl group-containing dispersant is preferred. The dispersant preferably contains a phosphorus-containing organic compound. A particularly suitable example of the dispersant is a phosphorus-containing organic compound having a phosphate group.
[0064] The phosphorus-containing organic compound is preferably easily decomposed or evaporated by light and / or heat. By using an organic substance that is easily decomposed or evaporated by light and / or heat, organic residues are less likely to remain after firing, and metal wiring with low resistivity can be obtained.
[0065] The decomposition temperature of the phosphorus-containing organic compound is not limited, but is preferably 600° C. or lower, more preferably 400° C. or lower, and even more preferably 200° C. or lower. From the viewpoint of the stability of the phosphorus-containing organic compound, the decomposition temperature may be preferably 60° C. or higher, 90° C. or higher, or 120° C. or higher. In the present disclosure, the decomposition temperature is the decomposition onset temperature determined by thermogravimetric differential thermal analysis.
[0066] The boiling point of the phosphorus-containing organic compound is not limited, but is preferably 300° C. or lower, more preferably 200° C. or lower, and even more preferably 150° C. or lower. From the viewpoint of stability of the phosphorus-containing organic compound, the boiling point may be preferably 60° C. or higher, 90° C. or higher, or 120° C. or higher.
[0067] The absorption characteristics of the phosphorus-containing organic compound are not limited, but it is preferable that the phosphorus-containing organic compound can absorb the laser light used for firing. In the present disclosure, the ability to absorb the laser light used for firing means that the absorption coefficient at a wavelength of 532 nm measured by an ultraviolet-visible spectrophotometer is 0.10 cm -1 More specifically, a phosphorus-containing organic compound that absorbs light having an emission wavelength (center wavelength) of, for example, 355 nm, 405 nm, 445 nm, 450 nm, 532 nm, or 1064 nm as the emission wavelength (center wavelength) of the laser light used for firing is preferred. In particular, when the substrate is a resin substrate, a phosphorus-containing organic compound that absorbs light having a center wavelength of 355 nm, 405 nm, 445 nm, and / or 450 nm is preferred.
[0068] It is preferable that the phosphorus-containing organic compound is a phosphoric acid ester from the viewpoint of improving the stability of the dispersion in the atmosphere. [ka] (In the formula, R is a monovalent organic group.) The phosphoric acid monoester represented by the formula (I) is preferred in that it has excellent adsorption to metal oxide particles and exhibits appropriate adhesion to the substrate, thereby contributing to both stable formation of metal wiring and good development of unexposed areas. Examples of R include substituted or unsubstituted hydrocarbon groups.
[0069] An example of a phosphoric acid monoester is represented by the following formula (2): [ka] Examples of the compound include compounds having a structure represented by the following formula:
[0070] An example of a phosphoric acid monoester is represented by the following formula (3): [ka] (In the formula, l, m, and n each independently represent an integer of 1 to 20.) Compounds having a structure represented by the following formula are also exemplified.
[0071] In the above formula (3), l is an integer of 1 to 20, preferably an integer of 1 to 15, and more preferably an integer of 1 to 10; m is an integer of 1 to 20, preferably an integer of 1 to 15, and more preferably an integer of 1 to 10; and n is an integer of 1 to 20, preferably an integer of 1 to 15, and more preferably an integer of 1 to 10.
[0072] Examples of organic structures that the phosphorus-containing organic compounds have include polyethylene glycol (PEG), polypropylene glycol (PPG), polyimide, polyester (e.g., polyethylene terephthalate (PET), polyethylene naphthalate (PEN)), polyethersulfone (PES), polycarbonate (PC), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyacetal, polyarylate (PAR), polyamide (PA), polyamideimide (PAI), polyetherimide (PEI), polyphenylene ether (PPE), polyphenylene sulfide (PPS), polyetherketone (PEK), polyphthalamide (PPA), polyethernitrile (PENt), polybenzimidazole (PBI), polycarbodiimide, polysiloxane, polymethacrylamide, nitrile rubber, acrylic rubber, polyethylene tetrafluoride, epoxy resin, The polyisoprene may have a structure derived from a compound such as phenol resin, melamine resin, urea resin, polymethylmethacrylate resin (PMMA), polybutene, polypentene, ethylene-propylene copolymer, ethylene-butene-diene copolymer, polybutadiene, polyisoprene, ethylene-propylene-diene copolymer, butyl rubber, polymethylpentene (PMP), polystyrene (PS), styrene-butadiene copolymer, polyethylene (PE), polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), polyether ether ketone (PEEK), phenol novolac, benzocyclobutene, polyvinylphenol, polychloropyrene, polyoxymethylene, polysulfone (PSF), polysulfide, silicone resin, aldose, cellulose, amylose, pullulan, dextrin, glucan, fructan, chitin, etc. (specifically, the structure may be derived from a compound such as chitin (specifically, the structure may be derived from a compound such as chitin) (specifically, the structure may be derived from a compound such as chitin (specifically, the structure may be derived from a compound such as chitin) (specifically, the structure may be derived from a compound such as chitin (specifically, the structure may be derived from a compound such as chitin)). A phosphorus-containing organic compound having a polymer skeleton selected from polyethylene glycol, polypropylene glycol, polyacetal, polybutene, and polysulfide is preferred because it is easily decomposed and is unlikely to leave a residue in the metal wiring obtained after firing.
[0073] Specific examples of the phosphorus-containing organic compound include commercially available materials, specifically, DISPERBYK (registered trademark)-102, DISPERBYK-103, DISPERBYK-106, DISPERBYK-109, DISPERBYK-110, DISPERBYK-111, DISPERBYK-118, DISPERBYK-140, DISPERBYK-145, DISPERBYK-168, DISPERBYK-180, DISPERBYK-182, DISPERBYK-187, DISPERBYK-190, DISPERBYK-191, DISPERBYK-193, DISPERBYK-194N, DISPERBYK-199, DISPERBYK-2000, DISPERBYK-2001, Examples of such surfactants include DISPERBYK-2008, DISPERBYK-2009, DISPERBYK-2010, DISPERBYK-2012, DISPERBYK-2013, DISPERBYK-2015, DISPERBYK-2022, DISPERBYK-2025, DISPERBYK-2050, DISPERBYK-2152, DISPERBYK-2055, DISPERBYK-2060, DISPERBYK-2061, DISPERBYK-2164, DISPERBYK-2096, DISPERBYK-2200, BYK (registered trademark)-405, BYK-607, BYK-9076, BYK-9077, BYK-P105, Plysurf (registered trademark) M208F and Plysurf DBS manufactured by Daiichi Kogyo Seiyaku Co., Ltd. These may be used alone or in combination.
[0074] In the dispersion and the dried coating film, the content of the dispersant may be 5 parts by volume or more and 900 parts by volume or less, when the total volume of the metal particles and the metal oxide particles is 100 parts by volume. The lower limit is preferably 10 parts by volume or more, more preferably 30 parts by volume or more, and even more preferably 60 parts by volume or more. The upper limit is preferably 480 parts by volume or less, more preferably 240 parts by volume or less.
[0075] In terms of parts by mass, the content of the dispersant relative to a total of 100 parts by mass of metal particles and metal oxide particles is preferably 1 part by mass or more and 150 parts by mass or less. The lower limit is preferably 2 parts by mass or more, more preferably 5 parts by mass or more, and even more preferably 10 parts by mass or more. The upper limit is preferably 80 parts by mass or less, more preferably 40 parts by mass or less. If the content of the dispersant is 5 parts by volume or more or 1 part by mass or more, a thin film with a thickness of submicrons can be easily formed. If the content of the dispersant is 10 parts by volume or more or 5 parts by mass or more, a thick film with a thickness of, for example, several tens of μm can be easily formed. If the content of the dispersant is 30 parts by volume or more or 10 parts by mass or more, a highly flexible dried coating film that is unlikely to crack even when bent can be obtained. If the content of the dispersant is 900 parts by volume or less or 150 parts by mass or less, good metal wiring can be obtained by firing.
[0076] The content of the dispersant in the dispersion is preferably 0.10% by mass or more and 20% by mass or less, more preferably 0.20% by mass or more and 15% by mass or less, and even more preferably 1.0% by mass or more and 8.0% by mass or less, based on the total dispersion. When the content is 20% by mass or less, the conductive film obtained by firing tends to have good conductivity without much residue derived from the dispersant. In addition, when the content is 0.10% by mass or more, the metal particles and / or metal oxide particles do not aggregate, and good dispersibility can be obtained.
[0077] ((iii) Reducing Agent) The dispersion and the dried coating may further contain a reducing agent. The reducing agent may remain in the dispersion due to its use in the synthesis of the particle components, which are metal particles and / or metal oxide particles, and therefore remain in the dried coating. The reducing agent preferably contains hydrazine and / or hydrazine hydrate, more preferably hydrazine and / or hydrazine hydrate. When the dispersion contains metal oxide particles and the dried coating contains a reducing agent, the metal oxide (e.g., copper oxide) is easily reduced to a metal (e.g., copper) when the dried coating is irradiated with a laser beam, and the resistance of the reduced metal (e.g., copper) can be reduced. The reducing agent remains in the unexposed area of the dried coating (i.e., the area not irradiated with the laser beam).
[0078] The mass ratio of the content of the reducing agent in the dispersion and in the dried coating film to the total content of the metal particles and metal oxide particles is preferably 0.0001 or more, or 0.0010 or more, or 0.0020 or more, or 0.0040 or more, from the viewpoint of obtaining a good reduction effect, and is preferably 0.10 or less, or 0.050 or less, or 0.030 or less, from the viewpoint of avoiding excess remaining reducing agent and obtaining low-resistance metal wiring.
[0079] In addition, it is preferable that the total content of hydrazine and hydrazine hydrate (based on the amount of hydrazine) and the content of copper oxide in the dispersion and the dried coating film satisfy the following relationship. 0.0001≦(hydrazine mass / copper oxide mass)≦0.10
[0080] ((iv) Dispersion medium) The dispersion medium is contained in the dispersion and the dried coating film in order to disperse the particle components, which are metal particles and / or metal oxide particles.
[0081] Specific examples of the dispersion medium include alcohols (monohydric alcohols and polyhydric alcohols (e.g., glycols)), ethers of alcohols (e.g., glycols), and esters of alcohols (e.g., glycols). More specific examples include: Propylene glycol monomethyl ether acetate, 3-methoxy-3-methyl-butyl acetate, ethoxyethyl propionate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol tertiary butyl ether, dipropylene glycol monomethyl ether, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol butyl ether, Ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 2-pentanediol, 2-methylpentane-2,4-diol, 2,5-hexanediol, 2,4-heptanediol, 2-ethylhexane-1,3-diol, diethylene glycol, dipropylene glycol, hexanediol, octanediol, triethylene glycol, tri-1,2-propylene glycol, glycerol, ethyl acetate, normal propyl acetate, isopropyl acetate, Pentane, hexane, octane, nonane, decane, cyclohexane, methylcyclohexane, toluene, xylene, mesitylene, ethylbenzene, Methyl ethyl ketone, methyl isobutyl ketone, dimethyl carbonate, Examples of the alcohol include methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, sec-butanol, t-butanol, n-pentanol, i-pentanol, sec-pentanol, t-pentanol, 2-methylbutanol, 3-methoxybutanol, n-hexanol, sec-hexanol, 2-methylpentanol, 2-ethylbutanol, sec-heptanol, 3-heptanol, n-octanol, sec-octanol, 2-ethylhexanol, n-nonyl alcohol, 2,6-dimethyl-4-heptanol, n-decanol, cyclohexanol, methylcyclohexanol, 3,3,5-trimethylcyclohexanol, phenol, benzyl alcohol, and diacetone alcohol.
[0082] Among these, from the viewpoint of dispersibility of metal particles and / or metal oxide particles, monoalcohols or polyhydric alcohols having 10 or less carbon atoms are more preferred. Among the monoalcohols having 10 or less carbon atoms, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, sec-butanol, and t-butanol are even more preferred. These alcohols may be used alone or in combination.
[0083] The solid content of the dispersion is preferably 0.6% by mass or more and 80% by mass or less, more preferably 1.2% by mass or more and 75% by mass or less, and even more preferably 6.0% by mass or more and 58% by mass or less. The solid content of the dispersion can be determined by measuring 0.5 to 1.0 g of the dispersion, heating it in air at 60°C for 4.5 hours, and dividing the weight after heating by the weight before heating. In one embodiment, the solid content of the dispersion corresponds to the content of particle components, which are metal particles and / or metal oxide particles, in the dispersion. When the solid content is 0.6% by mass or more and 80% by mass or less, the dispersion can have a viscosity suitable for application to a substrate.
[0084] The viscosity of the dispersion is preferably 0.1 mPa·s or more and 100,000 mPa·s or less, more preferably 0.1 mPa·s or more and 10,000 mPa·s or less, and even more preferably 1 mPa·s or more and 1,000 mPa·s or less. When the viscosity is 0.1 mPa·s or more and 100,000 mPa·s or less, the dispersion can be applied more uniformly to the substrate. In the present disclosure, the viscosity is a value measured by an E-type viscometer.
[0085] The pH of the dispersion is preferably 4.0 or more, or 5.0 or more, or 6.0 or more from the viewpoint of preventing dissolution of the metal particles and / or metal oxide particles in the dispersion, and may be, for example, 10.0 or less, or 9.0 or less, or 8.0 or less from the viewpoint of reducing damage to the substrate.
[0086] The surface free energy of the dispersion is preferably 10 mN / m or more, or 12 mN / m or more, or 15 mN / m or more, and is preferably 50 mN / m or less, or 35 mN / m or less, or 25 mN / m or less, so that the dispersion can be applied uniformly and without unevenness to a substrate.
[0087] The thickness of the dried coating film is preferably 0.1 μm or more, or 0.5 μm or more, or 1.0 μm or more from the viewpoint of easily producing metal wiring having low resistance and excellent mechanical properties, and may be preferably 50 μm or less, or 25 μm or less, or 10 μm or less from the viewpoint of producing fine-sized metal wiring with high precision.
[0088] [Base material] The substrate constitutes a surface on which the metal wiring is disposed. The substrate is preferably made of an insulating material in order to ensure electrical insulation between the metal wiring formed by the laser light. However, it is not necessary that the entire substrate is made of an insulating material. It is sufficient that only the portion constituting the surface on which the metal wiring is disposed is made of an insulating material.
[0089] Moreover, the material of the substrate is preferably a material with a heat resistance of 60° C. or higher in order to prevent the substrate from being burned by the laser light and generating smoke when irradiated with the laser light. The substrate does not need to be made of a single material, and for example, glass fiber may be added to the resin in order to increase the heat resistance temperature.
[0090] The surface of the substrate on which the dried coating film is disposed may be flat or curved, or may be a surface including steps. More specifically, the substrate may be a substrate (e.g., a plate, a film, or a sheet) or a three-dimensional object (e.g., a housing, etc.). The plate is, for example, a support used in a circuit board such as a printed circuit board. The film or sheet is, for example, a base film that is a thin-film insulator used in a flexible printed circuit board.
[0091] Examples of the three-dimensional object include the housings of electrical devices such as mobile phone terminals, smartphones, smart glasses, televisions, personal computers, etc. Other examples of the three-dimensional object include dashboards, instrument panels, steering wheels, chassis, etc. in the automotive field.
[0092] Specific examples of the substrate include a substrate made of an inorganic material (hereinafter referred to as an "inorganic substrate"), and a substrate made of a resin (hereinafter referred to as a "resin substrate").
[0093] The inorganic substrate is composed of, for example, glass, silicon, mica, sapphire, quartz, clay film, ceramic material, etc. The ceramic material is selected from, for example, alumina, silicon nitride, silicon carbide, zirconia, yttria, aluminum nitride, and a mixture of at least two of these. In addition, as the inorganic substrate, a substrate composed of glass, sapphire, quartz, etc., which has particularly high light transmittance, can be used.
[0094] Examples of the resin substrate include polypropylene (PP), polyimide (PI), polyester (polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), etc.), polyethersulfone (PES), polycarbonate (PC), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyacetal (POM), polyarylate (PAR), polyamide (PA) (PA6, PA66, etc.), polyamideimide (PAI), polyetherimide (PEI), polyphenylene ether (PPE), modified polyphenylene ether (m-PPE), polyphenylene sulfide (PPS), polyetherketone (PEK), polyetheretherketone (PEEK), polyphthalamide (PPA), polyethernitrile (PENt), polybenzimidazole (PBI), polycarbodiimide, polymethacrylamide, nitrile rubber, acrylic rubber, polyethylene tetrafluoride, epoxy resin, Supports made of, for example, polymethylmethacrylate resin (PMMA), polybutene, polypentene, ethylene-propylene copolymer, ethylene-butene-diene copolymer, polybutadiene, polyisoprene, ethylene-propylene-diene copolymer, butyl rubber, polymethylpentene (PMP), polystyrene (PS), styrene-butadiene copolymer, polyethylene (PE), polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), phenol novolac, benzocyclobutene, polyvinylphenol, polychloropyrene, polyoxymethylene, polysulfone (PSF), polyphenylsulfone resin (PPSU), cycloolefin polymer (COP), acrylonitrile-butadiene-styrene resin (ABS), acrylonitrile-styrene resin (AS), polytetrafluoroethylene resin (PTFE), polychlorotrifluoroethylene (PCTFE), and silicone resin can be used.
[0095] In addition to the above, for example, a resin sheet containing cellulose nanofibers can also be used as the substrate.
[0096] In particular, at least one selected from the group consisting of PI, PET, and PEN has excellent adhesion to metal wiring, is readily available in the market, and is available at low cost, which is advantageous from a business perspective and is therefore preferable.
[0097] Furthermore, at least one selected from the group consisting of PP, PA, ABS, PE, PC, POM, PBT, m-PPE and PPS is excellent in adhesion to metal wiring, particularly in the case of a housing, and is also excellent in moldability and mechanical strength after molding.Furthermore, these materials are preferable because they have heat resistance sufficient to withstand laser light irradiation when forming metal wiring.
[0098] Furthermore, the material of the three-dimensional object is preferably at least one selected from the group consisting of polypropylene resin, polyamide resin, acrylonitrile butadiene styrene resin, polyethylene resin, polycarbonate resin, polyacetal resin, polybutylene terephthalate resin, modified polyphenylene ether resin, and polyphenylene sulfide resin.
[0099] The deflection temperature under load of the resin substrate is preferably 400°C or less, more preferably 280°C or less, and even more preferably 250°C or less. Substrates having a deflection temperature under load of 400°C or less are available at low cost and are advantageous and preferable from the viewpoint of business. From the viewpoint of the handleability of the resin substrate, the deflection temperature under load is preferably 70°C or more, 80°C or more, 90°C or more, or 100°C or more. The deflection temperature under load of the present disclosure is a value obtained in accordance with JIS K7191.
[0100] The thickness of the substrate, for example in the case of a plate, film or sheet, is preferably 1 μm or more, or 25 μm or more, and preferably 100 mm or less, or 10 mm or less, or 250 μm or less. When the thickness of the substrate is 250 μm or less, the electronic device to be produced can be made lighter, more space-saving and more flexible, which is preferable.
[0101] In addition, when the substrate is a three-dimensional object, its maximum dimension (i.e., the maximum length of one side) is preferably 1 μm or more, or 200 μm or more, and preferably 1000 mm or less, or 100 mm or less, or 5 mm or less, in order to satisfactorily express the mechanical strength and heat resistance of the substrate.
[0102] [Metal Wiring Manufacturing Process] 1 is a diagram illustrating an example of a method for producing a metal wiring according to the present embodiment. Hereinafter, an example embodiment of each step will be described with reference to FIG.
[0103] (Preparation of Dispersion) In one embodiment, a dispersion is prepared prior to the coating step. In the following, a case where a dispersion containing cuprous oxide particles is prepared will be described as an example. The cuprous oxide particles can be synthesized, for example, by the following method. (1) A method in which water and a copper acetylacetonate complex are added to a polyol solvent, the organocopper compound is heated to dissolve, and then the amount of water required for the reaction is further added and the mixture is reduced by heating to the reduction temperature of the organocopper. (2) A method in which an organic copper compound (copper-N-nitrosophenylhydroxylamine complex) is heated to a high temperature of about 300°C in an inert atmosphere in the presence of a protective agent such as hexadecylamine. (3) A method of reducing copper salt dissolved in an aqueous solution with hydrazine (Figure 1(a)).
[0104] The above method (1) can be carried out, for example, under the conditions described in Angewandte Chemie International Edition, No. 40, Vol. 2, p. 359, 2001.
[0105] The above method (2) can be carried out, for example, under the conditions described in Journal of the American Chemical Society, 1999, Vol. 121, p. 11595.
[0106] In the above method (3), a divalent copper salt can be suitably used as the copper salt, and examples thereof include copper acetate (II), copper nitrate (II), copper carbonate (II), copper chloride (II), copper sulfate (II), etc. The amount of hydrazine used is preferably 0.2 mol to 2 mol, more preferably 0.25 mol to 1.5 mol, per mol of the copper salt.
[0107] A water-soluble organic substance may be added to the aqueous solution in which the copper salt is dissolved. By adding the water-soluble organic substance to the aqueous solution, the melting point of the aqueous solution is lowered, so that reduction can be carried out at a lower temperature. As the water-soluble organic substance, for example, alcohol, water-soluble polymer, etc. can be used.
[0108] Examples of alcohol include: Monohydric alcohols such as methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, sec-butanol, t-butanol, n-pentanol, i-pentanol, sec-pentanol, t-pentanol, 2-methylbutanol, 2-ethylbutanol, 3-methoxybutanol, n-hexanol, sec-hexanol, 2-methylpentanol, sec-heptanol, 3-heptanol, n-octanol, sec-octanol, 2-ethylhexanol, n-nonyl alcohol, 2,6-dimethyl-4-heptanol, n-decanol, cyclohexanol, methylcyclohexanol, 3,3,5-trimethylcyclohexanol, phenol, benzyl alcohol, and diacetone alcohol; glycols such as ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 2-pentanediol, 2-methylpentane-2,4-diol, 2,5-hexanediol, 2,4-heptanediol, 2-ethylhexane-1,3-diol, diethylene glycol, dipropylene glycol, hexanediol, octanediol, triethylene glycol, tri-1,2-propylene glycol, etc.; polyhydric alcohols such as glycerin, etc.; glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol tertiary butyl ether, and dipropylene glycol monomethyl ether; Glycol esters such as propylene glycol monomethyl ether acetate; etc. As the water-soluble polymer, for example, polyethylene glycol, polypropylene glycol, polyethylene glycol-polypropylene glycol copolymer, etc. can be used.
[0109] The temperature during reduction in the above method (3) can be, for example, −20° C. to 60° C., and is preferably −10° C. to 30° C. This reduction temperature may be constant during the reaction, or may be increased or decreased during the reaction. In the early stage of the reaction when the activity of hydrazine is high, reduction is preferably performed at 10° C. or lower, and more preferably at 0° C. or lower. The reduction time is preferably 30 minutes to 300 minutes, and more preferably 90 minutes to 200 minutes. The reduction is preferably performed in an inert atmosphere such as nitrogen or argon.
[0110] Among the above methods (1) to (3), method (3) is preferable since it is easy to operate and can give particles having a small particle size.
[0111] Next, the reaction solution is centrifuged to separate the supernatant and precipitate (Figure 1(b)), and the copper oxide particles are collected as the precipitate.
[0112] On the other hand, commercially available copper oxide particles may be used, such as cuprous oxide particles having an average primary particle size of 18 nm sold by EM Japan.
[0113] Next, a dispersion medium and, in one embodiment, a dispersant are added to the copper oxide particles, and the mixture is stirred by a known method such as a homogenizer to disperse the copper oxide particles in the dispersion medium (FIG. 1(c)).
[0114] Depending on the dispersion medium, the copper oxide particles may be difficult to disperse and may be insufficiently dispersed. In such a case, it is preferable to disperse the copper oxide using, for example, an alcohol in which the copper oxide particles are easily dispersed, such as butanol, and then replace the solvent with a desired dispersion medium and concentrate to a desired concentration. Examples include a method of concentrating using an ultrafiltration (UF) membrane and a method of repeatedly diluting and concentrating with a desired dispersion medium. For example, the desired dispersion can be obtained by the above procedure (Figure 1(d)). In addition, the liquid recovered from development can be concentrated by vacuum distillation or membrane distillation to obtain a dispersion with a desired solid content. In addition, the liquid recovered from development can be mixed with the dispersion prepared above for use.
[0115] (polishing process) In one embodiment, the dispersion-coated surface of the substrate (FIG. 1(e)) may have a controlled arithmetic mean surface roughness. In a typical embodiment, the arithmetic mean surface roughness of the substrate surface is controlled by polishing the substrate surface. That is, in one embodiment, the substrate has a polished surface (FIG. 1(f)). In the present disclosure, polishing includes both smoothing and roughening. The polishing method is not particularly limited, but may include, for example, a physical polishing method using a grindstone (rotary grindstone, etc.), a file, abrasive paper, abrasive, etc., and a chemical polishing method using electrolytic polishing, solvent immersion, etc. An appropriate polishing method may be selected depending on the material and surface morphology of the substrate surface to be polished, the desired arithmetic mean surface roughness value, etc.
[0116] The arithmetic mean surface roughness Ra of the dispersion-coated surface of the substrate is preferably 70 nm or more, or 100 nm or more, or 150 nm or more, and may be preferably 10,000 nm or less, or 5,000 nm or less, or 1,000 nm or less. In the present disclosure, the arithmetic mean surface roughness Ra is a value measured using a stylus-type surface profiler. The surface roughness of a substrate on which a coating film has already been disposed can be measured by the following method. The substrate on which the coating film has been disposed is immersed in 0.6 mass% nitric acid or hydrochloric acid in an amount that immerses the entire substrate, and is shaken at a speed of 60 rpm for 12 hours or more to dissolve the coating film. After the coating film has completely dissolved, the substrate is washed with 50 ml or more of ultrapure water, and then measured with a stylus-type surface profiler.
[0117] When the value of the arithmetic mean surface roughness Ra is 70 nm or more, the dispersion enters the recesses of the uneven shape of the substrate surface by the anchor effect, so that the dried coating film and the substrate are well adhered to each other, and a metal wiring that is difficult to peel off even when a developing operation is performed is formed. This is preferable because the damage to the metal wiring during the developing operation is less, and the resistance of the metal wiring is less likely to increase after development. In addition, when the value of the arithmetic mean surface roughness Ra is 10,000 nm or less, the uneven shape of the surface of the substrate is not excessively large, so that a coating film can be formed on the surface with a uniform thickness. Therefore, it is possible to obtain a metal wiring that is less likely to break and has less variation in resistance value between parts. In addition, the value of the arithmetic mean surface roughness Ra is 10,000 nm or less, which is also advantageous in terms of good development removability of the unexposed parts.
[0118] (Coating process) In this process, a dispersion layer is formed by applying a dispersion onto the surface of a substrate with a controlled arithmetic mean surface roughness (FIG. 1(g)). The method for forming the dispersion layer is not particularly limited, but coating methods such as die coating, spin coating, slit coating, bar coating, knife coating, spray coating, and dip coating can be used. It is desirable to apply the dispersion to a uniform thickness on the substrate using these methods.
[0119] (drying process) In this step, the substrate and the dispersion layer formed on the substrate are dried to form a dry coating film (FIG. 1(h)). Drying conditions may be adjusted so that the solid content of the dry coating film is controlled to a desired range (the ranges listed in the present disclosure in one embodiment).
[0120] The drying temperature is preferably 40° C. or more, or 50° C. or more, or 60° C. or more, in terms of being able to shorten the drying time and increase industrial productivity, and is preferably 120° C. or less, or 110° C. or less, or 100° C. or less, or 90° C. or less, in terms of being able to suppress deformation of the substrate (particularly the resin substrate). The drying time is preferably 8 hours or less, or 4 hours or less, or 2 hours or less from the viewpoint of preventing excessive volatilization of the dispersion medium in the dispersion layer, controlling the solid content rate of the dried coating film to a desired level, and thereby facilitating dispersion of the dried coating film during development (i.e., improving developability). In addition, the drying time is preferably 10 minutes or more, or 20 minutes or more, or 30 minutes or more from the viewpoint of preventing a trace amount of dispersion medium contained in the dried coating film from reacting with the substrate (particularly a resin substrate), dissolving the substrate and diffusing into the dried coating film, strengthening the bond between the dried coating film and the substrate, and suppressing deterioration of developability, and reducing the content of organic components contained in the metal wiring formed in the laser light irradiation step described below, thereby producing low-resistance metal wiring. The drying pressure may typically be normal pressure. In terms of increasing industrial productivity, reduced pressure may be performed, and may be preferably -0.05 MPa or less, or -0.1 MPa or less in gauge pressure. By the drying step as described above, a structure with a dried coating film having a substrate and a dried coating film arranged on the substrate can be formed.
[0121] The solid content of the dry coating film is preferably 60% by mass or more and 99% by mass or less, more preferably 65% by mass or more and 95% by mass or less, and even more preferably 70% by mass or more and 90% by mass or less. In the present disclosure, the solid content of the dry coating film can be measured using a TG-DTA (thermogravimetric differential thermal analysis) device. If the solid content of the dry coating film is 60% by mass or more, the volume shrinkage of the dry coating film when irradiating laser light to obtain metal wiring is small, the amount of voids in the metal wiring is small, and sintering properties are high, so that wiring with low resistance and small variation in resistance value between parts can be obtained. In addition, if the solid content of the dry coating film is 60% by mass or more, the adhesion or bonding strength between the unexposed part and the substrate is small, and good development removability can be obtained. For example, when the substrate is a resin substrate, the substrate may be slightly dissolved by the dispersion medium in the dry coating film, and the substrate components may diffuse into the dry coating film, resulting in strong bonding between the unexposed part and the substrate, but if the solid content is 60% by mass or more, such diffusion can be avoided. On the other hand, when the solid content of the dried coating film is 99 mass% or less, the metal particles and / or metal oxide particles in the dried coating film disperse well in the developer, and the amount of metal particles and / or metal oxide particles remaining on the substrate after development can be reduced (i.e., the developability is good).
[0122] (Storage process) In one embodiment, a storage step may be performed in which the structure with the dried coating is stored for a predetermined time. In the storage step, the storage temperature is preferably 0° C. or higher, or 5° C. or higher, or 10° C. or higher, and preferably 40° C. or lower, or 30° C. or lower. Furthermore, the relative humidity is preferably 20% or higher, or 30% or higher, and preferably 70% or lower, or 50% or lower. When the structure with the dried coating is stored, deterioration of the coating components and migration may occur, and migration may cause a short circuit in the metal wiring. When the storage temperature and relative humidity are within the above ranges, the dried coating is stably stored, and deterioration and migration of the coating components can be suppressed. The pressure during storage may typically be normal pressure, but may be reduced, and may be preferably -0.05 MPa or lower, or -0.1 MPa or lower in gauge pressure.
[0123] The storage time of the structure with the dried coating is preferably 10 minutes or more, or 20 minutes or more, or 30 minutes or more, in order to allow the heat generated during the drying process to be released and to suppress changes in the coating composition due to the dry coating absorbing moisture from the air, thereby suppressing variations in the resistance value of the metal wiring formed by laser irradiation in the laser light irradiation process described below, and is preferably 60 days or less, or 30 days or less, or 7 days or less, in order to prevent deterioration of developability due to a trace amount of dispersion medium contained in the dried coating reacting with the substrate (particularly a resin substrate), causing the substrate to dissolve and diffuse into the dried coating, thereby strengthening the bond between the dried coating and the substrate.
[0124] (Laser light irradiation process) In this process, the dried coating film is irradiated with laser light (FIG. 1(i)) to form a conductive portion-attached structure having a substrate and a film having conductive portions (exposed portions) and non-conductive portions (unexposed portions) arranged on the substrate (FIG. 1(j)). The conductive portions are formed as metal wiring. For example, when a dispersion containing copper oxide particles is used, the copper oxide in the dried coating film is reduced in the laser light irradiation process to generate copper particles, and heat treatment is performed under conditions in which the generated copper particles are fused together to form an integrated structure, thereby forming metal wiring.
[0125] For the laser light irradiation, a known laser light irradiation device having a laser light irradiation unit may be used. Laser light is preferable in that it is possible to expose the dry coating film formed on the substrate to high temperature for a short time by short-time exposure to high-intensity light, and to bake the film. The laser light method is advantageous in that it can shorten the baking time, causing less damage to the substrate, and can be applied to substrates with low heat resistance (e.g., resin film substrates). In addition, the laser light method is also advantageous in that it allows a large degree of freedom in wavelength selection, and the wavelength can be selected taking into consideration the light absorption wavelength of the dry coating film and / or the light absorption wavelength of the substrate.
[0126] Furthermore, the laser light method allows exposure by beam scanning, making it easy to adjust the exposure range; for example, it is possible to selectively irradiate (draw) light onto only the desired areas of the dried coating film without using a mask.
[0127] The types of laser light source that can be used include YAG (yttrium aluminum garnet), YVO (yttrium vanadate), Yb (ytterbium), semiconductor lasers (GaAs, GaAlAs, GaInAs), carbon dioxide, etc. As for the laser, not only the fundamental wave but also higher harmonics can be extracted and used as necessary.
[0128] The central wavelength of the laser light is preferably 350 nm or more and 600 nm or less. In particular, when cuprous oxide is used as the metal oxide, the cuprous oxide absorbs the laser light having a central wavelength in the above range well, and is uniformly reduced, so that a low-resistance metal wiring can be formed.
[0129] The dried coating film is preferably irradiated with the laser light through a galvanometer scanner. By scanning the dried coating film with the laser light by the galvanometer scanner, metal wiring of any shape can be obtained.
[0130] The irradiation output of the laser light is preferably 100 mW or more, or 200 mW or more, or 300 mW or more from the viewpoint of efficiently performing the desired firing (e.g., reduction of cuprous oxide), and is preferably 1500 mW or less, or 1250 mW or less, or 1000 mW or less from the viewpoint of obtaining low-resistance metal wiring by suppressing destruction of the metal wiring due to ablation caused by excessive output of the laser light.
[0131] In one embodiment, the laser light may be repeatedly scanned at a desired position on the dried coating film. In this case, it is preferable to set the movement amount of the laser light to such an amount that adjacent scanning lines overlap each other. FIG. 2 is a schematic diagram illustrating overlapping irradiation of the laser light in the manufacturing method of the metal wiring according to this embodiment. Referring to FIG. 2, the first scanning line R1 and the adjacent second scanning line R2 overlap each other. This increases the amount of heat storage in the overlapping region where the first scanning line R1 and the second scanning line R2 overlap, thereby increasing the degree of sintering of the copper particles, and as a result, the resistance value of the metal wiring can be lowered.
[0132] The overlap ratio S can be calculated from the width S1 of the first scanning line R1 of the laser light and the width S2 of the second scanning line R2 overlapping with the first scanning line R1 in a direction perpendicular to the scanning length direction, using the following formula. S = S2 / S1 x 100 (%)
[0133] The overlap rate is preferably in the range of 5% to 99.5%, more preferably in the range of 10% to 99.5%, and even more preferably in the range of 15% to 99.5%. By setting the overlap rate to 5% or more, the degree of sintering of the metal wiring can be increased and the amount of smoke generated can be suppressed. By setting the overlap rate to 99.5% or less, the dried coating film can be sintered while moving the laser light in a direction perpendicular to the scanning length direction at an industrially practical speed. According to the overlap rate in the above range, the degree of sintering of the metal wiring can be increased compared to, for example, an overlap rate below the above range, so that a non-brittle and hard metal wiring can be manufactured. As a result, for example, even when the metal wiring is formed on a flexible substrate and bent, the metal wiring can follow the flexible substrate without cracking.
[0134] (Development process) In this process, the unexposed parts of the dried coating film are developed and removed with a developer (FIG. 1(k)). The form of development is not particularly limited. For example, the conductive portion-attached structure may be immersed in the developer and shaken, the conductive portion-attached structure may be immersed in the developer and then irradiated with ultrasonic waves using an ultrasonic device, or the developer may be directly sprayed onto the conductive portion-attached structure using a spray or the like.
[0135] The developing step includes a first developing treatment using a first developer and a second developing treatment using a second developer. In one embodiment, the developing step is a combination of one or more first developing treatments using a first developer and one or more second developing treatments using a second developer. The types of developers in the two or more first developing treatments may be the same or different from each other, and similarly, the types of developers in the two or more second developing treatments may be the same or different from each other. For example, a combination of a developer containing a dispersant and a developer not containing a dispersant may be used as the first or second developer. In this case, it is preferable to perform development using a developer containing a dispersant and then development using a developer not containing a dispersant, since the residual dispersant on the conductive portion-attached structure can be reduced.
[0136] The combination of the first and second development processes provides a high dispersion effect of the coating film in the developer, and the removability of the unexposed area is good. In the development process, it is preferable to use the first and second developers separately (i.e., not mix them) by replacing them. By replacing the developers, the coating film can be more effectively dispersed in the developer, and the developability can be improved.
[0137] The developing step may further include an additional developing process using the additional developer of the present disclosure in addition to the first and second developing processes. The timing of the additional developing process is not limited. For example, when the second developing process is performed after the first developing process, the additional developing process may be performed before the first developing process, between the first developing process and the second developing process, and / or after the second developing process.
[0138] The compositions of the first developer, the second developer, and the additional developer may be different from each other, or two or more of them may be the same. The preferred embodiments of the additional developer may be the same as those listed in this disclosure for the first developer and / or the second developer.
[0139] When the conductive portion-attached structure is immersed in a developer and ultrasonic irradiation is performed using an ultrasonic device, the ultrasonic irradiation time is preferably 1 minute or more and 30 minutes or less. Irradiation for 1 minute or more is highly effective in dispersing the coating film attached to the substrate, and irradiation for 30 minutes or less can suppress damage to the metal wiring.
[0140] In the developing step, it is preferable to use a jig for holding the conductive portion-attached structure. The shape of the jig is not particularly limited, but it is desirable to have a shape that can prevent damage or detachment of the metal wiring caused by contact between the conductive portion-attached structure and the bottom or side wall of a container that contains the developer during the developing operation, or by contact between the structures when multiple conductive portion-attached structures are developed simultaneously. The jig may be, for example, a jig having a recess for holding each of the conductive portion-attached structures, a clip for holding the structures, or the like.
[0141] 3 to 5 are schematic diagrams showing an example of a jig for holding a conductive portion-attached structure in a development step of the method for producing metal wiring according to the present embodiment. FIG. 3 shows an example in which a jig 12 having a rack portion 12a is placed in a container 11, and a conductive portion-attached structure 13 having a substrate 13a and a post-irradiation coating film 13b (i.e., a film having a conductive portion and a non-conductive portion) is placed on the rack portion 12a. FIG. 4 shows an example in which a jig 22 for forming a recessed portion 22a is placed in a container 21, and a conductive portion-attached structure 23 having a three-dimensional substrate 23a and a post-irradiation coating film 23b is inserted into the recessed portion 22a. FIG. 5 shows an example in which a container 31 functions as a jig by having a jig 32 portion for forming a recessed portion 32a, and a conductive portion-attached structure 33 having a three-dimensional substrate 33a and a post-irradiation coating film 33b is inserted into the recessed portion 32a. The recesses 22a, 32a shown in FIGS. 4 and 5 are particularly useful when a three-dimensional substrate is used.
[0142] In particular, when ultrasonic waves are applied to the conductive portion-equipped structure during development, the rack portion 12a shown in FIG. 3 and the recessed portions 22a, 32a shown in FIGS. 4 and 5 effectively prevent contact between the conductive portion-equipped structures.
[0143] It is more preferable that the jig has a structure that can hold the conductive portion-attached structure well while not preventing contact between the developer and the conductive portion-attached structure, for example a mesh-like structure.
[0144] Furthermore, the jig may have any desired member or shape, such as a lid for preventing the conductive portion-attached structure from floating up in the developer.
[0145] (Recovery and reuse of developing solution) In the present disclosure, the dispersion containing the particle component that is a metal particle and / or a metal oxide particle may be a dispersion (regenerated dispersion) prepared from a liquid containing a used developer recovered after the development step (used developer). The recovery method and preparation method of the used developer are described below.
[0146] There is no particular limitation on the method for recovering the used developer, but examples of the method include using a pump to extract the used developer in the development tank, draining the used developer from the bottom of the tank, and directly pouring the used developer from the development tank into a recovery tank. In addition, in order to recover the components in the developer uniformly and efficiently, the liquid may be transferred while being stirred. There is no particular limitation on the recovery tank, but a container that is resistant to the components of the developer, such as one made of SUS, polyethylene, or polypropylene, is preferred.
[0147] The used developer recovered as described above may be used to prepare a regenerated dispersion. It is preferable to recover the used developer and reuse it in the preparation of the dispersion from the viewpoint of effective use of resources and cost reduction by reducing waste. When the main component of the dispersant in the dispersion is the same as the main component of the dispersant in the developer, the developer can be reused more efficiently.
[0148] In particular, when the developer contains water and the developer after use is regenerated to obtain a regenerated dispersion, in addition to the advantage of reusing resources, the use of water also provides the advantage of regeneration at a lower cost and in a cleaner environment.
[0149] In one embodiment, the used developer can be reused as it is as a raw material for the dispersion by simply adjusting the concentration as necessary. In this case, for example, since there is no need to newly prepare a dispersant, it is possible to recover resources more efficiently.
[0150] With reference to Figures 6 and 7, the regenerated dispersion can be prepared by recovering the used developer and subjecting it to a regeneration process. The used developer may be partially or entirely reused. As the dispersion of the present disclosure, an unused dispersion (i.e., a newly prepared dispersion) or a regenerated dispersion, or a combination thereof, can be subjected to the coating process, and Figures 6 and 7 show an example in which a combination of an unused dispersion and a regenerated dispersion is subjected to the coating process. With reference to Figures 6 and 7, the unused dispersion and the regenerated dispersion are applied to a substrate, dried to form a dry coating film, and after laser light irradiation (i.e., baking), the wiring is completed by developing with a developer. The above-mentioned regenerated dispersion is formed by recovering a part or all of the used developer and subjecting it to a regeneration process.
[0151] Examples of the regeneration treatment include concentration adjustment (e.g., concentration or dilution), component adjustment (e.g., addition or removal of a specific component), purification (e.g., removal of impurities such as residues), and dispersion state adjustment (e.g., dispersion treatment). Prior to the regeneration treatment, the components of the used developer may be analyzed. In this case, the regeneration treatment conditions may be determined based on the obtained component analysis results. When the used developer contains a dispersant, it is preferable to carry out the regeneration treatment under conditions that avoid the deterioration or loss of the dispersant.
[0152] More specific examples of the regeneration treatment include one or more of (1) concentration, (2) addition of one or more of metal particles and / or metal oxide particles, a dispersant, a reducing agent, and a dispersion medium, and (3) dispersion treatment of the components in the used developer. When all of these treatments are performed, the order is not particularly limited, but the order of (1), (2), and (3) is preferred.
[0153] (1) Concentration The method for concentrating the used developer is not particularly limited, but examples thereof include a method of evaporating and concentrating by heating and reducing pressure using an evaporator or the like, a method of concentrating using a separation membrane, a method of drying once by freeze-drying or the like and then dispersing the obtained powder in a dispersion medium again, etc. By concentration, the solid content may be adjusted to preferably 5% by mass or more, or 10% by mass or more, and may also be adjusted to preferably 60% by mass or less, or 50% by mass or less.
[0154] (2) Addition In order to adjust the viscosity and / or the solid content, it is preferable to add one or more of the components exemplified above as the components of the dispersion, more specifically, one or more of metal particles and / or metal oxide particles, a dispersant, a reducing agent, and a dispersion medium to the used developer. In one embodiment, among the desired components of the dispersion, a component that is not contained in the used developer or is contained in the used developer in an amount less than the desired amount may be added.
[0155] (3) Distributed processing From the viewpoint of obtaining a high-quality regenerated dispersion, it is preferable to carry out a dispersion treatment of the components contained in the used developer. The dispersion method is not particularly limited, but for example, the used developer may be placed in a container and shaken continuously with a shaker to promote dispersion by the liquid flow, or a mechanical dispersion treatment may be carried out using a homogenizer or the like. From the viewpoint of the stability of the used developer, the dispersion time is preferably 1 minute or more. The longer the dispersion time, the better, but from the viewpoint of production efficiency, it may be, for example, 1 hour or less. When the above-mentioned (2) is also added, the dispersion treatment is preferably carried out after the addition of the above-mentioned (2).
[0156] The regenerated dispersion can be prepared through the above-mentioned treatment. The types of components contained in the regenerated dispersion, the content of each component, and various properties (solid content, viscosity, pH, surface free energy, etc.) may be the same as those described above for the dispersion.
[0157] <Kit containing a structure with a dried coating film or a structure with a conductive portion and a developer> Another aspect of the present invention provides a kit including the above-described dry-coated structure of the present disclosure and the above-described developer of the present disclosure. The dry-coated structure has a substrate and the dry coating of the present disclosure disposed on the surface of the substrate. That is, the dry coating includes, in one aspect, a particle component that is a metal particle and / or a metal oxide particle, and further includes, in one aspect, a dispersant and / or a reducing agent. Another aspect of the present invention provides a kit including the conductive portion-attached structure of the present disclosure and the developer of the present disclosure. The conductive portion-attached structure includes a substrate and a film having (1) a conductive portion region and (2) a non-conductive portion region disposed on a surface of the substrate. In one aspect, the conductive portion region (1) corresponds to an exposed portion of the present disclosure, and the non-conductive portion region (2) corresponds to an unexposed portion of the present disclosure. In one aspect, the conductive portion region (1) is a metal wiring containing copper. In one aspect, the non-conductive portion region (2) contains cuprous oxide, and in one aspect, further contains a dispersant and / or a reducing agent.
[0158] In each of the above kits, the developer includes the first developer of the present disclosure and the second developer of the present disclosure. In one embodiment, the first developer and / or the second developer includes water and / or an organic solvent (an alcohol-based solvent in one embodiment), and further includes a dispersant (A) in one embodiment, and includes the dispersant (A) in an amount of 0.1% by mass or more and 20% by mass or less in one embodiment. In another embodiment, the dried coating film includes a dispersant (B), and the main components of the dispersant (A) and the dispersant (B) are the same.
[0159] By using the above-mentioned structure with a dried coating film in combination with a developer, low-resistance metal wiring can be formed by irradiating the dried coating film with a laser beam, and the unexposed portion can be developed and removed satisfactorily without damaging the metal wiring, thereby producing a high-quality structure with metal wiring having a substrate and metal wiring arranged on the surface of the substrate. Also, by using the above-mentioned structure with a conductive portion in combination with a developer, the non-conductive portion can be developed and removed satisfactorily without damaging the conductive portion, which is the metal wiring, thereby producing a high-quality structure with metal wiring.
[0160] <Metal Wiring Manufacturing System> An embodiment of the present invention also provides a metal wiring manufacturing system. Referring to FIG. 8, in one embodiment, the metal wiring manufacturing system 100 includes: a coating mechanism 101 for coating a dispersion containing a particle component, which is metal particles and / or metal oxide particles, on a surface of a substrate to form a dispersion layer; a drying mechanism 102 for drying the dispersion layer to form a dried coated structure having a substrate and a dried coating disposed on the substrate; a laser light irradiation mechanism 103 for irradiating the dried coating film with a laser light to form metal wiring; a developing mechanism 104 for developing and removing the area of the dried coating film other than the metal wiring with a developer; Equipped with. The metal wiring manufacturing system of the present disclosure can be suitably applied to the metal wiring manufacturing method of the present disclosure. Therefore, each element of the metal wiring manufacturing system may have the configuration or function as exemplified above in the metal wiring manufacturing method.
[0161] The coating mechanism 101 may be, for example, one or more types selected from a die coater, a spin coater, a slit coater, a bar coater, a knife coater, a spray coater, a dip coater, and the like.
[0162] The drying mechanism 102 may be one or more types selected from an oven, a vacuum dryer, a nitrogen-injection dryer, an IR furnace, a hot plate, and the like.
[0163] The laser light irradiation mechanism 103 may include, for example, a laser light oscillator (not shown) and a galvano scanner (not shown) that irradiates the coating film with the oscillated laser light.
[0164] In one embodiment, the development mechanism 104 comprises: (1) a first developing unit 104a for developing the dried coating film with a first developer of the present disclosure; and (2) a second developing section 104b for developing the dried coating film with a second developer of the present disclosure; In one embodiment, the first developer and / or the second developer contain water and / or an organic solvent (an alcohol-based solvent in one embodiment), and further contain a dispersant in one embodiment, and contain the dispersant in an amount of 0.1 mass % or more and 20 mass % or less in one embodiment. The positional relationship between the first developing unit 104a and the second developing unit 104b is not limited, but from the viewpoint of the efficiency of removing metal particles and / or metal oxide particles, it is preferable that they are arranged so that the conductive portion-attached structure is supplied to the first developing unit 104a and then the second developing unit 104b, as shown in FIG.
[0165] In one embodiment, each of the first developing unit 104a and the second developing unit 104b may have a developer and a container for accommodating the developer and the conductive portion-attached structure. Each of the first developing unit 104a and the second developing unit 104b preferably has a mechanism for promoting development, such as one or more of a shaker for shaking the conductive portion-attached structure and an ultrasonic irradiator for irradiating the conductive portion-attached structure with ultrasonic waves. In one embodiment, each of the first developing unit 104a and the second developing unit 104b may be composed of a developer and a sprayer for spraying the developer onto the conductive portion-attached structure.
[0166] In one embodiment, the metal wiring manufacturing system 100 may further include a developer regeneration mechanism 105 that regenerates the developer recovered from the development mechanism 104 to generate a regenerated dispersion. The developer regeneration mechanism 105 may be, for example, a concentrator, a diluter, a mixer, an impurity remover, a disperser, or the like.
[0167] In addition to the above-mentioned elements, the metal wiring manufacturing system may include additional elements such as a substrate transport mechanism and a substrate cleaning mechanism, as desired.
[0168] <Application Examples> As described above, the method for producing metal wiring according to this embodiment, and the combination of a dried coating-film-attached structure or a conductive-portion-attached structure with a developer, can produce a metal wiring-attached structure with good developability while suppressing changes in the resistance value of the metal wiring due to development. The metal wiring-attached structure according to this embodiment can be suitably applied to, for example, metal wiring materials for electronic circuit boards (printed circuit boards, RFID, replacement for wire harnesses in automobiles, etc.), antennas formed on the housings of portable information devices (smartphones, etc.), mesh electrodes (electrode films for capacitive touch panels), electromagnetic wave shielding materials, and heat dissipation materials. EXAMPLES
[0169] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples and comparative examples.
[0170] <Evaluation method> [Arithmetic mean surface roughness Ra of substrate] The arithmetic average surface roughness Ra of the surface of the substrate to which the dispersion was applied was measured by the following method. The surface roughness of the substrate was measured using a stylus surface profiler (DektakXT manufactured by Bruker) and analysis software (Vision64). The measurement conditions were as follows: Scan Type: Standard Scan Range: 65.5μm Profile:Hills&Valleys Stylus type: Radius 12.5μm Stylus force: 1mg Length: 1000μm Hold time: 5 seconds Resolution: 0.666μm / pt After measuring the shape of the substrate surface, the surface roughness was analyzed under the following conditions: Filter Type: Gaussian Regression Long cutoff: Long cutoff applied, standard cutoff used (0.25mm) Roughness profile: Ra Parameter calculation: ISO4287 Sample length used in calculation: Automatic selection The average value of the surface roughness value obtained under the above conditions and the surface roughness value measured in a direction perpendicular to the above measurement direction was taken as the arithmetic mean surface roughness Ra of the substrate.
[0171] [Resistance of metal wiring and change in resistance before and after development] For each metal wiring of the conductive part structure in which three metal wirings are formed by laser light irradiation, a tester is placed at a position 0.5 mm from both ends in the longitudinal direction to measure the resistance value, and the number average value R of the three metal wirings is calculated. A The resistance value of the metal wiring after the conductive portion structure was developed was also measured in the same manner, and the number average value R of the three metal wirings was calculated. B was calculated. R B / R A A value of 10 or less was judged to be good, 5 or less to be better, and 2 or less to be even better. Good is indicated as △, better as ○, and even better as ◎. B / R A If the value is greater than 10, or if the resistance value cannot be measured due to a broken wire, the evaluation is indicated as ×.
[0172] [Solubility] 0.10 g of cuprous oxide powder (as a particle component that is a metal particle and / or a metal oxide particle) was added to 40 ml of the developer, and the solution was left to stand at room temperature of 25°C for 6 hours. The developer containing the powder was then filtered through a 0.2 μm filter and diluted 100 times (by mass) with 0.10 mol / L nitric acid. The metal concentration (unit: mg / L) of the resulting diluted solution was measured using an ICP light emitting device (manufactured by SII Nano Technology Co., Ltd.) and used as the solubility.
[0173] [Surface free energy] The measurement was performed by the pendant drop method using a contact angle meter (Model DM700, manufactured by Kyowa Interface Science Co., Ltd.). A syringe equipped with a 22G injection needle was filled with the measurement solution, and a 5 μL droplet was ejected from the needle. The surface free energy was calculated from the shape of the droplet at the needle tip using the Young-Laplace method.
[0174] [Developability of conductive structure] The developability was evaluated by the following method: The conductive structure produced in the laser light irradiation step (i.e., the structure including the copper wiring and the dry coating film not irradiated with the laser light) was immersed in a developer (23°C) in an amount sufficient to immerse the entire structure, and ultrasonic waves were irradiated for 1 minute or more and 30 minutes or less using an ultrasonic device to perform development.
[0175] After development, the portion of the substrate that did not have metal wiring was cut into 10 mm squares, attached to a sample stage for SEM (scanning electron microscope) with carbon tape, and coated with platinum-palladium using a coater (Vacuum Device MSP-1S). The coating conditions were set to process time: 1.5 minutes. The coated sample was measured for the remaining concentration of the applied metal on the substrate surface using an SEM (Hitachi High-Tech FlexSEM1000) and an EDX (energy dispersive X-ray analysis) device (Oxford Instruments AztecOne). The electron beam conditions were acceleration voltage: 5 kV, spot intensity: 80, focus position: 10 mm, and after focusing on the sample surface, the magnification was set to 200 times to perform mapping analysis of the entire field of view. The mapping acquisition conditions were resolution: 256, collection time: 50 frames, process time: high sensitivity, pixel dwell time: 150 μs, and frame live time: 0:00:08. The measurement elements were carbon, oxygen, nitrogen, and the metal elements applied (i.e., contained in the dispersion), and platinum and palladium used in the coating were not included in the measurement elements. Measurements were performed under the above conditions, and the obtained metal element concentration (mass%) was taken as the concentration of the metal that was not developed and remained on the substrate.
[0176] (Developability Evaluation Criteria) In the evaluation of the developability of the above-mentioned conductive structure, it was judged that if the concentration of the metal remaining on the substrate was 14% by mass or less, it was good, and if it was 2.0% by mass or less, it was even better. Good was indicated as ○, and even better as ◎. On the other hand, if the concentration of the metal remaining on the substrate was more than 14% by mass, or if the coating film was clearly not dispersed in the developer during the development operation and remained on the substrate, it was indicated as ×.
[0177] <Example 1> [Preparation of Dispersion] 3,224 g of copper(II) acetate monohydrate (manufactured by Nippon Kagaku Sangyo Co., Ltd.) was dissolved in a mixed solvent consisting of 30,240 g of water and 13,976 g of 1,2-propylene glycol (manufactured by Asahi Glass Co., Ltd.), 940 g of hydrazine hydrate (manufactured by Nippon Finechem Co., Ltd.) was added, and the mixture was stirred. The supernatant and precipitate were then separated using centrifugation.
[0178] To the resulting precipitate (858 g), 113 g of DISPERBYK-145 (trade name, manufactured by BYK-Chemie) (BYK-145) as a phosphorus-containing organic compound and 916 g of n-butanol (manufactured by Sankyo Chemical) as a dispersion medium were added, and the mixture was dispersed using a homogenizer under a nitrogen atmosphere to obtain a dispersion containing cuprous oxide particles containing cuprous oxide (copper (I) oxide). At this time, the solid residue (cuprous oxide particles) when the dispersion was heated at normal pressure and 60°C for 4.5 hours was 34.7 mass%. The surface free energy of the dispersion was measured to be 26 mN / m.
[0179] [Polishing of substrate] The surface of an ABS substrate (as a base material) having a width x depth x thickness of 50 mm x 50 mm x 1 mm was polished using abrasive paper #1000. After polishing, the arithmetic mean surface roughness Ra was measured and found to be 181 nm.
[0180] [Coating and drying the dispersion] The polished substrate was irradiated with ultrasonic waves for 5 minutes in ultrapure water, and then irradiated with ultrasonic waves for 5 minutes in ethanol for cleaning. Next, the surface of the substrate was subjected to UV ozone treatment, and 1 ml of the dispersion was dropped onto the surface, spin-coated (300 rpm, 300 seconds), and then heated and dried at 60°C for 1 hour. After drying, the substrate was stored for 10 minutes in a room at normal pressure, room temperature of 23°C, and relative humidity of 40%, to obtain a sample in which a dried coating film was formed on the substrate.
[0181] [Laser light irradiation] The above sample was placed in a box with a length of 200 mm, a width of 150 mm, and a height of 41 mm, the upper surface of which was made of quartz glass, with the dried coating film on the upper side. Compressed air was separated into nitrogen and oxygen by a separation membrane, and the separated nitrogen gas was blown into the box, so that the oxygen concentration in the box was 0.5 mass% or less. Next, the dried coating film was repeatedly irradiated with a laser beam (center wavelength 355 nm, frequency 300 kHz, pulse, output 79 mW) while scanning it, while moving the focal position on the substrate surface at a maximum speed of 25 mm / sec using a galvano scanner, to obtain a copper metal wiring with the desired dimensions of length 5 mm x width 1 mm. At this time, the laser beam was repeatedly irradiated while being moved in the scanning line width direction so that the overlap rate was 93.2%. Two more copper wirings were produced under the same conditions, resulting in a total of three copper wirings.
[0182] [Wiring resistance after laser irradiation] The resistance of the resulting metal wiring was measured by the method described above. The results were 10 Ω, 11 Ω, and 9.9 Ω for the three copper wirings, respectively. The average resistance before development was R A was 10 Ω.
[0183] [Developability of structure] The conductive part-attached structure after the laser irradiation was immersed in 50 ml (23°C) of 2% by mass DISPERBYK-145 aqueous solution (first developer) and irradiated with ultrasonic waves for 5 minutes using an ultrasonic cleaner (As One USD-4R), after which the structure was lifted up with tweezers and washed with 50 ml of running ultrapure water.Then, the structure was immersed again in 50 ml (23°C) of 5% by mass diethylenetriamine aqueous solution (second developer) and irradiated with ultrasonic waves for 1 minute, after which the structure was lifted up with tweezers and washed with 50 ml of running ultrapure water. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 0.2% by mass, and was evaluated as ⊚.
[0184] [Wiring resistance after development] After the development process, the resistance was measured using the method described above. The results were 11 Ω, 13 Ω, and 12 Ω for the three copper wirings, respectively. The average resistance after development was R Bwas 12 Ω. From this, R B / R A The score was 1.1 and the rating was ◎.
[0185] <Example 2> [Preparation of Dispersion] A dispersion was obtained in the same manner as in Example 1. [Polishing of substrate] The surface of an ABS substrate having a width x depth x thickness of 50 mm x 50 mm x 1 mm was polished using abrasive paper #2000. After polishing, the arithmetic mean surface roughness Ra was measured and found to be 245 nm. [Coating and drying the dispersion] Coating and drying were carried out in the same manner as in Example 1. [Laser light irradiation] Laser light irradiation was carried out in the same manner as in Example 1. [Wiring resistance after laser irradiation] The resistance of the resulting metal wiring was measured by the method described above. The results were 6.5 Ω, 7.3 Ω, and 7.2 Ω for the three copper wirings, respectively. The average resistance before development was R A was 7.0Ω. [Developability of structure] The conductive part-attached structure after the laser irradiation was immersed in 50 ml (23°C) of a 2% by mass DISPERBYK-145 aqueous solution (first developer) and irradiated with ultrasonic waves for 5 minutes using an ultrasonic cleaner (As One Corporation USD-4R), after which the structure was lifted up with tweezers and washed with 50 ml of running ultrapure water.Then, the structure was immersed in 50 ml (23°C) of ethanol (second developer) and irradiated with ultrasonic waves for 5 minutes, after which the structure was lifted up with tweezers and washed with 50 ml of running ultrapure water. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 8.6 mass %, and was evaluated as good. [Wiring resistance after development] After the development operation, the resistance was measured by the method described above. The results were 8.9 Ω, 7.3 Ω, and 7.3 Ω for the three copper wirings, respectively. The average resistance after development was R B was 7.8Ω. From this, R B / R AThe score was 1.1 and the rating was ◎.
[0186] <Example 3> [Preparation of Dispersion] A dispersion was obtained in the same manner as in Example 1. [Polishing of substrate] The surface of an ABS substrate having a width x depth x thickness of 50 mm x 50 mm x 1 mm was polished using abrasive paper #2000. After polishing, the arithmetic mean surface roughness Ra was measured and found to be 267 nm. [Coating and drying the dispersion] Coating and drying were carried out in the same manner as in Example 1. [Laser light irradiation] Laser light irradiation was carried out in the same manner as in Example 1. [Wiring resistance after laser irradiation] The resistance of the resulting metal wiring was measured by the method described above. The results were 4.8 Ω, 6.2 Ω, and 5.7 Ω for the three copper wirings, respectively. The average resistance before development was R A was 5.6 Ω. [Developability of structure] The developing operation was carried out in the same manner as in Example 1, except that the first developer was a 0.1% by mass aqueous solution of DISPERBYK-145, and the ultrasonic irradiation time in the first developer was 1 minute. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 2.3 mass %, and was evaluated as good. [Wiring resistance after development] After the development process, the resistance was measured using the method described above. The results were 6.8 Ω, 5.5 Ω, and 7.4 Ω for the three copper wirings, respectively. The average resistance after development was R B was 6.6Ω. From this, R B / R A The score was 1.2 and the rating was ◎.
[0187] <Example 4> [Preparation of Dispersion] A dispersion was obtained in the same manner as in Example 1. [Polishing of substrate] The surface of an ABS substrate having a width x depth x thickness of 50 mm x 50 mm x 1 mm was polished using abrasive paper #2000. After polishing, the arithmetic mean surface roughness Ra was measured and found to be 185 nm. [Coating and drying the dispersion] Coating and drying were carried out in the same manner as in Example 1. [Laser light irradiation] Laser light irradiation was carried out in the same manner as in Example 1. [Wiring resistance after laser irradiation] The resistance of the resulting metal wiring was measured by the method described above. The results were 9.0 Ω, 12 Ω, and 8.3 Ω for the three copper wirings, respectively. The average resistance before development was R A was 9.9 Ω. [Developability of structure] The developing operation was carried out in the same manner as in Example 1, except that the first developer was a 20% by mass aqueous solution of DISPERBYK-145, and the ultrasonic irradiation time in the first developer was 1 minute. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 4.2 mass %, and the evaluation was good. [Wiring resistance after development] After the development process, the resistance was measured using the method described above. The results were 11 Ω, 27 Ω, and 8.5 Ω for the three copper wirings, respectively. The average resistance after development was R B was 16 Ω. From this, R B / R A The score was 1.6, and the rating was ◎.
[0188] <Example 5> [Preparation of Dispersion] A dispersion was obtained in the same manner as in Example 1. [Polishing of substrate] The surface of an ABS substrate having a width x depth x thickness of 50 mm x 50 mm x 1 mm was polished using abrasive paper #2000. After polishing, the arithmetic mean surface roughness Ra was measured and found to be 235 nm. [Coating and drying the dispersion] Coating and drying were carried out in the same manner as in Example 1. [Laser light irradiation] Laser light irradiation was carried out in the same manner as in Example 1. [Wiring resistance after laser irradiation] The resistance of the resulting metal wiring was measured by the method described above. The results were 19 Ω, 21 Ω, and 26 Ω for the three copper wirings, respectively. The average resistance before development was R A was 22 Ω. [Developability of structure] The conductive part-attached structure after the laser light irradiation was immersed in 50 ml (23°C) of 20% by mass DISPERBYK-145 aqueous solution (first developer), and was irradiated with ultrasonic waves for 1 minute using an ultrasonic cleaner (USD-4R manufactured by AS ONE Corporation). The structure was then lifted up with tweezers and washed with 50 ml of running ultrapure water. The structure was then immersed in 50 ml (23°C) of 5% by mass diethylenetriamine aqueous solution (second developer), and was irradiated with ultrasonic waves for 1 minute. The structure was then lifted up with tweezers and washed with 50 ml of running ultrapure water. The structure was then immersed in 50 ml (23°C) of 5% by mass diethylenetriamine aqueous solution (third developer), and was irradiated with ultrasonic waves for 1 minute. The structure was then lifted up with tweezers and washed with 50 ml of running ultrapure water. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 0.4% by mass, and was evaluated as ⊚. [Wiring resistance after development] After the development process, the resistance was measured using the method described above. The results were 25 Ω, 34 Ω, and 31 Ω for the three copper wirings, respectively. The average resistance after development was R B was 30 Ω. From this, R B / R A The score was 1.4 and the rating was ◎.
[0189] <Example 6> [Preparation of Dispersion] 3,230 g of copper(II) acetate monohydrate (manufactured by Nippon Kagaku Sangyo Co., Ltd.) was dissolved in a mixed solvent consisting of 30,240 g of water and 13,980 g of 1,2-propylene glycol (manufactured by Asahi Glass Co., Ltd.), 940 g of hydrazine hydrate (manufactured by Nippon Finechem Co., Ltd.) was added, and the mixture was stirred under a nitrogen atmosphere, and then separated into a supernatant and a precipitate using centrifugation. 87 g of the mixture was added to 38 g of the obtained precipitate, and the mixture was dispersed using a homogenizer under a nitrogen atmosphere to obtain a dispersion containing cuprous oxide particles containing cuprous oxide (copper (I) oxide). The mixture was prepared by adding 8 g of Mix Ettal (Sankyo Chemical) as a dispersion medium to 131 g of DISPERBYK-118 (trade name, manufactured by BYK-Chemie) (BYK-118) as a phosphorus-containing organic compound. The solid residue (cuprous oxide particles) was 26.2 mass% when the dispersion was heated at normal pressure and 60°C for 4.5 hours.
[0190] [Polishing of substrate] The surface of an ABS substrate having a width x depth x thickness of 50 mm x 50 mm x 1 mm was polished using abrasive paper #2000. After polishing, the arithmetic mean surface roughness Ra was measured and found to be 205 nm. [Coating and drying the dispersion] Coating and drying were carried out in the same manner as in Example 1. [Laser light irradiation] Laser light irradiation was carried out in the same manner as in Example 1. [Wiring resistance after laser irradiation] The resistance of the resulting metal wiring was measured by the method described above. The results were 13 Ω, 21 Ω, and 31 Ω for the three copper wirings, respectively. The average resistance before development was R A was 22 Ω. [Developability of structure] The developing operation was carried out in the same manner as in Example 1, except that the first developer was a 2% by weight aqueous solution of DISPERBYK-118, and the ultrasonic irradiation time in the first developer was 1 minute. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 4.6 mass %, and was evaluated as good. [Wiring resistance after development] After the development process, the resistance was measured using the method described above. The results were 17Ω, 27Ω, and 37Ω for the three copper wirings, respectively. The average resistance after development was R B was 27 Ω. From this, R B / R A The score was 1.2 and the rating was ◎.
[0191] <Example 7> [Preparation of Dispersion] A dispersion was obtained in the same manner as in Example 1. [Polishing of substrate] The surface of an ABS substrate having a width x depth x thickness of 50 mm x 50 mm x 1 mm was polished using abrasive paper #2000. After polishing, the arithmetic mean surface roughness Ra was measured and found to be 208 nm. [Coating and drying the dispersion] Coating and drying were carried out in the same manner as in Example 1. [Laser light irradiation] Laser light irradiation was carried out in the same manner as in Example 1. [Wiring resistance after laser irradiation] The resistance of the resulting metal wiring was measured by the method described above. The results were 10 Ω, 4.0 Ω, and 5.8 Ω for the three copper wirings, respectively. The average resistance before development was R A was 6.6 Ω. [Developability of structure] The developing operation was carried out in the same manner as in Example 1, except that the first developer was a 2% by mass ethanol solution of DISPERBYK-145 (first developer) and the ultrasonic irradiation time in the first developer was 1 minute. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 5.1 mass %, and was evaluated as good. [Wiring resistance after development] After the development process, the resistance was measured using the method described above. The results were 18 Ω, 13 Ω, and 6.2 Ω for the three copper wirings, respectively. The average resistance after development was R B was 12 Ω. From this, R B / R A The score was 1.9, and the rating was ◎.
[0192] <Example 8> [Preparation of Dispersion] A dispersion was obtained in the same manner as in Example 1. [Polishing of substrate] The surface of an ABS substrate having a width x depth x thickness of 50 mm x 50 mm x 1 mm was polished using abrasive paper #2000. After polishing, the arithmetic mean surface roughness Ra was measured and found to be 285 nm. [Coating and drying the dispersion] Coating and drying were carried out in the same manner as in Example 1. [Laser light irradiation] Laser light irradiation was carried out in the same manner as in Example 1. [Wiring resistance after laser irradiation] The resistance of the resulting metal wiring was measured by the method described above. The results were 10 Ω, 7.5 Ω, and 6.5 Ω for the three copper wirings, respectively. The average resistance before development was R A was 8.0 Ω. [Developability of structure] The developing operation was carried out in the same manner as in Example 1, except that the ultrasonic irradiation time in the first developer was 1 minute, and the second developer was a 5% by mass aqueous solution of 2-aminoethanol. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 2.8 mass %, and was evaluated as good. [Wiring resistance after development] After the development, the resistance was measured by the method described above. The results were 23 Ω, 7.4 Ω, and 11 Ω for the three copper wirings, respectively. The average resistance after development was R B was 14 Ω. From this, R B / R A The score was 1.7, and the rating was ◎.
[0193] <Example 9> [Preparation of Dispersion] A dispersion was obtained in the same manner as in Example 1. [Polishing of substrate] The surface of an ABS substrate having a width x depth x thickness of 50 mm x 50 mm x 1 mm was polished using abrasive paper #2000. After polishing, the arithmetic mean surface roughness Ra was measured and found to be 175 nm. [Coating and drying the dispersion] Coating and drying were carried out in the same manner as in Example 1. [Laser light irradiation] Laser light irradiation was carried out in the same manner as in Example 1. [Wiring resistance after laser irradiation] The resistance of the resulting metal wiring was measured by the method described above. The results were 6.5 Ω, 7.1 Ω, and 6.5 Ω for the three copper wirings, respectively. The average resistance before development was R A was 6.7Ω. [Developability of structure] The developing operation was carried out in the same manner as in Example 1, except that the first developer was a 2% by weight aqueous solution of DISPERBYK-118, and the ultrasonic irradiation time in the first developer was 1 minute. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 6.3 mass %, and was evaluated as good. [Wiring resistance after development] After the development, the resistance was measured by the method described above. The results were 8.5Ω, 7.8Ω, and 8.2Ω for the three copper wirings, respectively. The average resistance after development was R B was 8.2Ω. From this, R B / R A The score was 1.2 and the rating was ◎.
[0194] <Example 10> [Preparation of Dispersion] A dispersion was obtained in the same manner as in Example 1. [Polishing of substrate] The surface of an ABS substrate having a width x depth x thickness of 50 mm x 50 mm x 1 mm was polished using abrasive paper #2000. After polishing, the arithmetic mean surface roughness Ra was measured and found to be 227 nm. [Coating and drying the dispersion] Coating and drying were carried out in the same manner as in Example 1. [Laser light irradiation] Laser light irradiation was carried out in the same manner as in Example 1. [Wiring resistance after laser irradiation] The resistance of the resulting metal wiring was measured by the method described above. The results were 10 Ω, 9.8 Ω, and 23 Ω for the three copper wirings, respectively. The average resistance before development was R A was 14 Ω. [Developability of structure] The developing operation was carried out in the same manner as in Example 1, except that the ultrasonic irradiation time in the first developer was 1 minute, and the second developer was a 5% by mass aqueous solution of N-methyldiethanolamine. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 9.4 mass %, and was evaluated as good. [Wiring resistance after development] After the development process, the resistance was measured using the method described above. The results were 13 Ω, 12 Ω, and 23 Ω for the three copper wirings, respectively. The average resistance after development was R B was 16 Ω. From this, R B / R A The score was 1.1 and the rating was ◎.
[0195] <Example 11> [Preparation of Dispersion] A dispersion was obtained in the same manner as in Example 1. [Polishing of substrate] The surface of an ABS substrate having a width x depth x thickness of 50 mm x 50 mm x 1 mm was polished using abrasive paper #2000. After polishing, the arithmetic mean surface roughness Ra was measured and found to be 139 nm. [Coating and drying the dispersion] Coating and drying were carried out in the same manner as in Example 1. [Laser light irradiation] Laser light irradiation was carried out in the same manner as in Example 1. [Wiring resistance after laser irradiation] The resistance of the resulting metal wiring was measured by the method described above. The results were 3.3 Ω, 2.4 Ω, and 5.7 Ω for the three copper wirings, respectively. The average resistance before development was R A was 3.8Ω. [Developability of structure] The developing operation was carried out in the same manner as in Example 1, except that the second developer was a 2% by weight aqueous solution of DISPERBYK-145, and the ultrasonic irradiation time in the second developer was 15 minutes. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 2.0% by mass, and was evaluated as ⊚. [Wiring resistance after development] After the development process, the resistance was measured using the method described above. The results were 21 Ω, 13 Ω, and 16 Ω for the three copper wirings, respectively. The average resistance after development was R B was 17Ω. From this, R B / R A The score was 4.5 and the rating was ○.
[0196] <Example 12> [Preparation of Dispersion] A dispersion was obtained in the same manner as in Example 1. [Polishing of substrate] The surface of an ABS substrate having a width x depth x thickness of 50 mm x 50 mm x 1 mm was polished using abrasive paper #2000. After polishing, the arithmetic mean surface roughness Ra was measured and found to be 212 nm. [Coating and drying the dispersion] Coating and drying were carried out in the same manner as in Example 1. [Laser light irradiation] Laser light irradiation was carried out in the same manner as in Example 1. [Wiring resistance after laser irradiation] The resistance of the resulting metal wiring was measured by the method described above. The results were 11 Ω, 18 Ω, and 18 Ω for the three copper wirings, respectively. The average resistance before development was R A was 16 Ω. [Developability of structure] The developing operation was carried out in the same manner as in Example 1, except that the first developer was ultrapure water, the ultrasonic irradiation time in the first developer was 1 minute, and the second developer was a 2 mass% aqueous solution of DISPERBYK-145. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 8.9 mass %, and was evaluated as good. [Wiring resistance after development] After the development process, the resistance was measured using the method described above. The results were 26 Ω, 27 Ω, and 16 Ω for the three copper wirings, respectively. The average resistance after development was R B was 22 Ω. From this, R B / R A The score was 1.4 and the rating was ◎.
[0197] [Preparation of regenerated dispersion] After the development operation, the first developer was recovered and then concentrated by heating at 80° C. to 8 ml to obtain a regenerated dispersion. [Coating and drying of regenerated dispersion] 1 ml of the above regenerated dispersion was dropped onto an ABS substrate with Ra of 6 nm, and dried by heating at 80° C. for 60 minutes. After drying, the sample was stored for 10 minutes in a room at normal pressure, room temperature of 23° C., and relative humidity of 40%, to obtain a sample with a dried coating film formed on the substrate. [Laser light irradiation] Laser light was irradiated in the same manner as in Example 1, except that the output was set to 135 mW and only one copper wiring was formed. [Wiring resistance after laser irradiation] The resistance of the resulting metal wiring was measured by the above-mentioned method and was found to be 1.0 Ω, indicating that a conductive metal wiring was obtained using the regenerated dispersion.
[0198] <Example 13> [Preparation of Dispersion] 3,224 g of copper(II) acetate monohydrate (manufactured by Nippon Kagaku Sangyo Co., Ltd.) was dissolved in a mixed solvent consisting of 30,240 g of water and 13,976 g of 1,2-propylene glycol (manufactured by Asahi Glass Co., Ltd.), 940 g of hydrazine hydrate (manufactured by Nippon Finechem Co., Ltd.) was added, and the mixture was stirred. The supernatant and precipitate were then separated using centrifugation. To 388 g of the obtained precipitate, 51 g of DISPERBYK-145 (trade name, manufactured by BYK-Chemie) (BYK-145) as a phosphorus-containing organic compound and 415 g of n-butanol (manufactured by Sankyo Chemical) as a dispersion medium were added, and the mixture was dispersed using a homogenizer under a nitrogen atmosphere to obtain a dispersion containing cuprous oxide particles containing cuprous oxide (copper (I) oxide). Furthermore, 7.3 g of BYK-145 and 115 g of n-butanol were added to 788 g of the obtained dispersion, and the mixture was dispersed using a homogenizer under a nitrogen atmosphere to obtain the desired dispersion. At this time, the solid residue (cuprous oxide particles) was 35.9 mass% when the dispersion was heated at normal pressure and 60 ° C for 4.5 hours. The surface free energy of the dispersion was measured to be 23 mNm.
[0199] [Polishing of substrate] A polycarbonate (PC) substrate with dimensions of 50 mm x 50 mm x 1 mm was used without polishing. The arithmetic mean surface roughness Ra was measured to be 4 nm. [Coating and drying the dispersion] The polished substrate was irradiated with ultrasonic waves for 5 minutes in ultrapure water, and then irradiated with ultrasonic waves for 5 minutes in ethanol for cleaning. Next, the surface of the substrate was subjected to UV ozone treatment, and 1 ml of the dispersion was dropped onto the surface, followed by heating and drying at 60°C for 2 hours. After drying, the substrate was stored for 10 minutes in a room at normal pressure, room temperature of 23°C, and relative humidity of 40%, to obtain a sample in which a dried coating film was formed on the substrate. [Laser light irradiation] Laser light irradiation was carried out in the same manner as in Example 1, except that the output was set to 395 mW. [Wiring resistance after laser irradiation] The resistance of the resulting metal wiring was measured by the method described above. The results were 0.17Ω, 0.17Ω, and 0.18Ω for the three copper wirings, respectively. The average resistance before development was R A was 0.17Ω. [Developability of structure] The developing operation was carried out in the same manner as in Example 1, except that the first developer was 30 ml of a 0.1% by mass aqueous solution of DISPERBYK-145, the amount of the second developer was 30 ml, and the ultrasonic irradiation time in the second developer was 5 minutes. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 0.2% by mass, and was evaluated as ⊚. [Wiring resistance after development] After the development, the resistance was measured by the method described above. The results were 0.16Ω, 0.15Ω, and 0.15Ω for the three copper wirings, respectively. The average resistance after development was R B was 0.15Ω. From this, R B / R A The score was 0.9 and the rating was ◎. [Preparation of regenerated dispersion] After the development operation, the first developer was recovered and then concentrated by heating at 60° C. to 10 ml to obtain a regenerated dispersion. [Coating and drying of regenerated dispersion] 1 ml of the above regenerated dispersion was dropped onto a PC substrate with Ra of 3 nm, and dried by heating at 60° C. for 30 minutes. After drying, the sample was stored for 10 minutes in a room at normal pressure, room temperature of 23° C., and relative humidity of 40%, to obtain a sample with a dried coating film formed on the substrate. [Laser light irradiation] Laser light was irradiated in the same manner as in Example 1, except that the output was set to 135 mW and only one copper wiring was formed. [Wiring resistance after laser irradiation] The resistance of the resulting metal wiring was measured by the above-mentioned method and was found to be 1.1 Ω, indicating that a conductive metal wiring was obtained using the regenerated dispersion.
[0200] <Example 14> [Preparation of Dispersion] A dispersion was prepared in the same manner as in Example 1. [Polishing of substrate] The surface of an ABS substrate having dimensions of 50 mm x 50 mm x 1 mm was not polished. The arithmetic mean surface roughness Ra was measured to be 256 nm. [Coating and drying the dispersion] The coating was carried out in the same manner as in Example 1. [Laser light irradiation] Laser light irradiation was carried out in the same manner as in Example 1. [Measuring wiring resistance after laser irradiation] When the resistance was measured using the method described above, the results were 6.3 Ω, 6.5 Ω, and 8.4 Ω for the three copper wirings, respectively. The average resistance before development was R A was 7.1 Ω. [Developability of structure] After the laser irradiation, the conductive part-attached structure was immersed in 50 ml of ultrapure water (23°C) and irradiated with ultrasonic waves for 5 minutes using an ultrasonic cleaner (As One Corp. USD-4R), after which the structure was lifted up with tweezers and washed with 50 ml of running ultrapure water.Then, the structure was immersed in another 50 ml of ultrapure water (23°C) and irradiated with ultrasonic waves for 5 minutes, after which the structure was lifted up with tweezers and washed with 50 ml of running ultrapure water. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 13.3 mass %, and was evaluated as good. [Measurement of wiring resistance after development] After the development process, the resistances of the three copper wirings were measured by the method described above. The resistances were 6.6Ω, 7.5Ω, and 8.9Ω, respectively, with an average value of 7.7Ω. B / R A The score was 1.1 and the rating was ◎.
[0201] <Example 15> [Preparation of Dispersion] A dispersion was prepared in the same manner as in Example 1. [Polishing of substrate] The surface of an ABS substrate having dimensions of 50 mm x 50 mm x 1 mm was not polished. The arithmetic mean surface roughness Ra was measured to be 236 nm. [Coating and drying the dispersion] The coating was carried out in the same manner as in Example 1. [Laser light irradiation] Laser light irradiation was carried out in the same manner as in Example 1. [Measuring wiring resistance after laser irradiation] When the resistance was measured using the method described above, the results were 36 Ω, 35 Ω, and 28 Ω for the three copper wirings, respectively. The average resistance before development was R A was 33 Ω. [Developability of structure] The developing operation was carried out in the same manner as in Example 1, except that the ultrasonic irradiation time in the first developing step was 1 minute and ultrapure water was used as the second developing solution. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 10.4 mass %, and the evaluation was good. [Measurement of wiring resistance after development] After the development process, the resistances of the three copper wirings were measured by the method described above. The resistances were 41Ω, 31Ω, and 33Ω, respectively, with an average value of 37Ω. B / R A The score was 1.1 and the rating was ◎.
[0202] <Example 16> [Preparation of Dispersion] A dispersion was prepared in a manner similar to that of Example 13. [Polishing of substrate] The surface of an ABS substrate with a width x depth x thickness of 50 mm x 50 mm x 1 mm was polished using abrasive paper #2000. After polishing, the arithmetic mean surface roughness Ra was measured and found to be 186 nm. [Coating and drying the dispersion] Coating was carried out in the same manner as in Example 13. [Laser light irradiation] Laser light irradiation was carried out in the same manner as in Example 13. [Measuring wiring resistance after laser irradiation] When the resistance was measured using the method described above, the results were 0.18Ω, 0.17Ω, and 0.17Ω for the three copper wirings, respectively. The average resistance before development was R A was 0.17Ω. [Developability of structure] The development operation was carried out in the same manner as in Example 13. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 0.1% by mass, and was evaluated as ⊚. [Measurement of wiring resistance after development] After the development, the resistance was measured by the method described above. The results were 0.19Ω, 0.15Ω, and 0.15Ω for the three copper wirings, respectively. The average resistance after development was R B was 0.16Ω. From this, R B / R A The score was 0.9 and the rating was ◎. [Preparation of regenerated dispersion] After the development operation, the first developer was recovered and then concentrated by heating at 60° C. to 10 ml to obtain a regenerated dispersion. [Coating and drying of regenerated dispersion] 1 ml of the above regenerated dispersion was dropped onto an ABS substrate with Ra of 6 nm, and dried by heating at 80° C. for 60 minutes. After drying, the sample was stored for 10 minutes in a room at normal pressure, room temperature of 23° C., and relative humidity of 40%, to obtain a sample with a dried coating film formed on the substrate. [Laser light irradiation] Laser light was irradiated in the same manner as in Example 1, except that the output was set to 135 mW and only one copper wiring was formed. [Wiring resistance after laser irradiation] The resistance of the resulting metal wiring was measured by the above-mentioned method and was found to be 1.0 Ω, indicating that a conductive metal wiring was obtained using the regenerated dispersion.
[0203] <Comparative Example 1> [Preparation of Dispersion] A dispersion was prepared in the same manner as in Example 1. [Polishing of substrate] The surface of an ABS substrate having dimensions of 50 mm x 50 mm x 1 mm was not polished. The arithmetic mean surface roughness Ra was measured to be 230 nm. [Coating and drying the dispersion] The coating was carried out in the same manner as in Example 1. [Laser light irradiation] Laser light irradiation was carried out in the same manner as in Example 1. [Measuring wiring resistance after laser irradiation] When the resistance was measured using the method described above, the results were 5.5 Ω, 4.6 Ω, and 5.0 Ω for the three copper wirings, respectively. The average resistance before development was R A was 5.0 Ω. [Developability of structure] After the laser light irradiation, the conductive structure was immersed in 50 ml of ultrapure water (23°C) and irradiated with ultrasonic waves for 5 minutes using an ultrasonic cleaner (As One USD-4R). The structure was then lifted up with tweezers and washed with 50 ml of running ultrapure water. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 14.3 mass %, and the evaluation was poor. [Measurement of wiring resistance after development] After the development process, the resistances of the three copper wirings were measured by the method described above. The resistances were 6.5Ω, 6.8Ω, and 5.9Ω, respectively, with an average value of 6.4Ω. B / R A The score was 1.3 and the rating was ◎.
[0204] <Comparative Example 2> [Preparation of Dispersion] A dispersion was prepared in the same manner as in Example 1. [Polishing of substrate] The surface of an ABS substrate having dimensions of 50 mm x 50 mm x 1 mm was not polished. The arithmetic mean surface roughness Ra was measured to be 327 nm. [Coating and drying the dispersion] The coating was carried out in the same manner as in Example 1. [Laser light irradiation] Laser light irradiation was carried out in the same manner as in Example 1. [Measuring wiring resistance after laser irradiation] When the resistance was measured using the method described above, the results were 21 Ω, 15 Ω, and 27 Ω for the three copper wirings, respectively. The average resistance before development was R A was 21 Ω. [Developability of structure] The developing operation was carried out in the same manner as in Example 1, except that the first developer was a 25% by mass aqueous solution of DISPERBYK-145, the ultrasonic irradiation time in the first development was 1 minute, and the second development was not performed. After the above-mentioned developing operation, the copper concentration in the portion of the substrate on which no metal wiring was present was measured by the above-mentioned method, and it was found to be 18.0 mass %, resulting in an evaluation of x. [Measurement of wiring resistance after development] After the development process, the resistances of the three copper wirings were measured by the method described above. The resistances were 14Ω, 16Ω, and 34Ω, respectively, with an average value of 21Ω. B / R A The score was 1.0, and the rating was ◎.
[0205] The above results are summarized in Tables 1 and 2, and the developability levels were the best in Examples 1, 5, 11, 13, and 16, followed by Examples 2 to 4, 6 to 10, 12, 14, and 15. In Comparative Examples 1 and 2, the concentration of copper remaining in the substrate after development was high, and development was insufficient.
[0206] [Table 1]
[0207] [Table 2] [Industrial Applicability]
[0208] According to the present invention, metal particles and / or metal oxide particles in unexposed areas can be efficiently removed in the development step, and since there is little change in resistance before and after development, it is possible to provide a low-resistance metal wiring structure that can avoid problems such as deposition outside the pattern in the subsequent plating step, short circuits due to migration, etc. Furthermore, according to a specific embodiment of the present invention, waste can be reduced by reusing the developer.
[0209] Such metal wiring structures can be suitably used as metal wiring materials for electronic circuit boards and the like, mesh electrodes, electromagnetic wave shielding materials, heat dissipation materials, and the like. [Explanation of symbols]
[0210] R1 1st scan line R2 Second scan line S1 width S2 width 11,21,31 container 12,22,32 Jig 12a Rack section 22a, 32a Recess 13, 23, 33 Conductive structure 13a,23a,33a Base material 13b,23b,33b Paint film after irradiation 100 Metal Wiring Manufacturing System 101 Coating mechanism 102 Drying mechanism 103 Laser light irradiation mechanism 104 Development mechanism 104a First developing unit 104b Second developing section 105 Developer regeneration mechanism
Claims
1. a coating step of coating a dispersion containing a particle component, which is metal particles and / or metal oxide particles, on a surface of a substrate to form a dispersion layer; drying the dispersion layer to form a dried coated structure having the substrate and a dried coating disposed on the substrate; a laser light irradiation step of irradiating the dried coating film with a laser light to form metal wiring; A developing step of developing and removing an area of the dried coating film other than the metal wiring with a developer, The developing step comprises: (1) a first development process in which the dried coating film is developed with a first developer; and (2) a second development process in which the dried coating film is developed with a second developer; Including, each of the first developer and the second developer contains water and / or an organic solvent; A method for producing a metal wiring, wherein a difference between a surface free energy of the first developer and a surface free energy of the dispersion is 0 mN / m or more and 50 mN / m or less.
2. 2. The method for producing a metal wiring according to claim 1, wherein the solubility of the particulate component in the second developer is higher than the solubility of the particulate component in the first developer.
3. The method for producing a metal wiring according to claim 1 or 2, wherein the particulate component is copper particles and / or copper oxide particles.
4. 4. The method for producing a metal wiring according to claim 3, wherein the solubility of the particulate component in the second developer is from 0.1 mg / L to 10,000 mg / L.
5. a coating step of coating a dispersion containing a particle component, which is metal particles and / or metal oxide particles, on a surface of a substrate to form a dispersion layer; drying the dispersion layer to form a dried coated structure having the substrate and a dried coating disposed on the substrate; a laser light irradiation step of irradiating the dried coating film with a laser light to form metal wiring; A developing step of developing and removing an area of the dried coating film other than the metal wiring with a developer, The developing step comprises: (1) a first development process in which the dried coating film is developed with a first developer; and (2) a second development process in which the dried coating film is developed with a second developer; Including, each of the first developer and the second developer contains water and / or an organic solvent; A method for manufacturing a metal wiring, wherein the solubility of the particulate component in the second developer is higher than the solubility of the particulate component in the first developer.
6. The method for producing a metal wiring according to claim 5 , wherein the particulate component is copper particles and / or copper oxide particles.
7. 7. The method for producing a metal wiring according to claim 6, wherein the solubility of the particulate component in the second developer is from 0.1 mg / L to 10,000 mg / L.
8. a coating step of coating a dispersion containing a particle component, which is metal particles and / or metal oxide particles, on a surface of a substrate to form a dispersion layer; drying the dispersion layer to form a dried coated structure having the substrate and a dried coating disposed on the substrate; a laser light irradiation step of irradiating the dried coating film with a laser light to form metal wiring; A developing step of developing and removing an area of the dried coating film other than the metal wiring with a developer, The developing step comprises: (1) a first development process in which the dried coating film is developed with a first developer; and (2) a second development process in which the dried coating film is developed with a second developer; Including, each of the first developer and the second developer contains water and / or an organic solvent; The particle component is copper particles and / or copper oxide particles, A method for producing a metal wiring, wherein the solubility of the particulate component in the second developer is 0.1 mg / L or more and 10,000 mg / L or less.
9. the first developer comprises water and / or an alcohol-based solvent; 9. The method for producing a metal wiring according to claim 1, wherein the second developer contains an organic solvent.
10. 10. The method for producing a metal wiring according to claim 1, wherein the first developer and / or the second developer contains an alcohol-based solvent.
11. 11. The method for producing a metal wiring according to claim 1, wherein the first developer and / or the second developer contains an amine-based solvent.
12. The method for producing a metal wiring according to claim 11, wherein the amine-based solvent contains diethylenetriamine and / or 2-aminoethanol.
13. The method for producing a metal wiring according to any one of claims 1 to 12, wherein the first developer and / or the second developer contains 0.1 mass % or more and 20 mass % or less of a dispersant (A).
14. The method for producing a metal wiring according to claim 13, wherein the dispersant (A) is a phosphorus-containing organic compound.
15. 15. The method for producing a metal wiring according to claim 13, wherein the dispersion contains a dispersant (B), and the main components of the dispersant (A) and the dispersant (B) are the same.
16. The method for producing a metal wiring according to any one of claims 1 to 15, further comprising a step of recovering a used developer after the developing step.
17. The method for producing a metal wiring according to any one of claims 1 to 16, wherein the dispersion is prepared from a solution containing a used developer recovered after the developing step.
18. A kit comprising a dried coated structure and a developer, The dry coated structure has a substrate and a dry coating film that is disposed on a surface of the substrate and includes a particulate component that is a metal particle and / or a metal oxide particle, the developer comprises a first developer and a second developer, each of the first developer and the second developer contains water and / or an organic solvent; the solubility of the particulate component in the second developer is greater than the solubility of the particulate component in the first developer.
19. 20. The kit of claim 18, wherein the particulate component is copper particles and / or copper oxide particles.
20. The kit described in claim 19, wherein the solubility value of the particle component in the second developer is 0.1 mg / L or more and 10,000 mg / L or less.
21. A kit comprising a dried coated structure and a developer, The dry coated structure has a substrate and a dry coating film that is disposed on a surface of the substrate and includes a particulate component that is a metal particle and / or a metal oxide particle, the developer comprises a first developer and a second developer, each of the first developer and the second developer contains water and / or an organic solvent; The particle component is copper particles and / or copper oxide particles, A kit, wherein the solubility value of the particle component in the second developer is 0.1 mg / L or more and 10,000 mg / L or less.
22. The kit according to any one of claims 18 to 21, wherein the organic solvent is an alcohol-based solvent.
23. The kit according to any one of claims 18 to 22, wherein the first developer and / or the second developer contains 0.1% by mass or more and 20% by mass or less of a dispersant (A).
24. The kit according to claim 23, wherein the dry coating film contains a dispersant (B), and the main components of the dispersant (A) and the dispersant (B) are the same.
25. a coating mechanism for coating a dispersion containing a particle component, which is metal particles and / or metal oxide particles, on a surface of a substrate to form a dispersion layer; a drying mechanism for drying the dispersion layer to form a dried coated structure having the substrate and a dried coating disposed on the substrate; a laser light irradiation mechanism for irradiating the dried coating film with a laser light to form metal wiring; a developing mechanism for developing and removing an area of the dried coating film other than the metal wiring with a developer; A metal wiring manufacturing system comprising: The developing mechanism includes: (1) a first developing section for developing the dried coating film with a first developer; and (2) a second developing section for developing the dried coating film with a second developer; having each of the first developer and the second developer contains water and / or an organic solvent; A metal wiring manufacturing system, wherein a difference between a surface free energy of the first developer and a surface free energy of the dispersion is 0 mN / m or more and 50 mN / m or less.
26. A metal wiring manufacturing system as described in claim 25, wherein the solubility of the particle component in the second developer is higher than the solubility of the particle component in the first developer.
27. A metal wiring manufacturing system as described in claim 25 or 26, wherein the particulate component is copper particles and / or copper oxide particles.
28. A metal wiring manufacturing system as described in claim 27, wherein the solubility value of the particle component in the second developer is 0.1 mg / L or more and 10,000 mg / L or less.
29. a coating mechanism for coating a dispersion containing a particle component, which is metal particles and / or metal oxide particles, on a surface of a substrate to form a dispersion layer; a drying mechanism for drying the dispersion layer to form a dried coated structure having the substrate and a dried coating disposed on the substrate; a laser light irradiation mechanism for irradiating the dried coating film with a laser light to form metal wiring; a developing mechanism for developing and removing an area of the dried coating film other than the metal wiring with a developer; A metal wiring manufacturing system comprising: The developing mechanism includes: (1) a first developing section for developing the dried coating film with a first developer; and (2) a second developing section for developing the dried coating film with a second developer; having each of the first developer and the second developer contains water and / or an organic solvent; A metal wiring manufacturing system, wherein the solubility of the particulate component in the second developer is higher than the solubility of the particulate component in the first developer.
30. The metal wiring manufacturing system described in claim 29, wherein the particulate component is copper particles and / or copper oxide particles.
31. A metal wiring manufacturing system as described in claim 30, wherein the solubility value of the particle component in the second developer is 0.1 mg / L or more and 10,000 mg / L or less.
32. a coating mechanism for coating a dispersion containing a particle component, which is metal particles and / or metal oxide particles, on a surface of a substrate to form a dispersion layer; a drying mechanism for drying the dispersion layer to form a dried coated structure having the substrate and a dried coating disposed on the substrate; a laser light irradiation mechanism for irradiating the dried coating film with a laser light to form metal wiring; a developing mechanism for developing and removing an area of the dried coating film other than the metal wiring with a developer; A metal wiring manufacturing system comprising: The developing mechanism includes: (1) a first developing section for developing the dried coating film with a first developer; and (2) a second developing section for developing the dried coating film with a second developer; having each of the first developer and the second developer contains water and / or an organic solvent; The particle component is copper particles and / or copper oxide particles, A metal wiring manufacturing system, wherein the solubility value of the particulate component in the second developer is 0.1 mg / L or more and 10,000 mg / L or less.
33. The metal wiring manufacturing system according to any one of claims 25 to 32, wherein the organic solvent is an alcohol-based solvent.
34. The metal wiring manufacturing system according to any one of claims 25 to 33, wherein the first developer and / or the second developer contains 0.1 mass% or more and 20 mass% or less of a dispersant (A).
Citation Information
Patent Citations
Wiring substrate and information memory medium using metallic oxide
JP1993037126A
Formation of electrical conductors on substrates
JP2008505494A
Method for manufacturing metal wiring substrate and metal wiring substrate formed by using it
JP2009004669A
Ecological method for constructing circuit boards
JP2015076611A
Metallic copper dispersion, process for producing the metallic copper dispersion, electrode, wiring pattern, and coating film formed using the metallic copper dispersion, decorative article and antimicrobial article with the coating film formed thereon, and processes for producing the decorative article and the antimicrobial article
WO2010024385A1